Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2020)
A dataset containing 939029643 species occurrences available in GBIF matching the query: { "and" : [ { "or" : [ "BasisOfRecord is Observation", "BasisOfRecord is Machine Observation", "BasisOfRecord is Human Observation", "BasisOfRecord is Material sample", "BasisOfRecord is Literature Occurrence", "BasisOfRecord is Specimen", "BasisOfRecord is Living Specimen" ] }, { "or" : [ "Issue is Coordinate rounded", "Issue is Geodetic datum assumed WGS84", "Issue is Coordinate reprojected", "Issue is Country derived from coordinates" ] }, "HasCoordinate is true", "HasGeospatialIssue is false" ] } The dataset includes 939029643 records from 16397 constituent datasets: 1285 records from Suivi des aires marines protégées de Moorea - Invertébrés benthiques. 4 records from New and little known species of Lepechinella (Crustacea, Amphipoda, Lepechinellidae) and an allied new genus Lepesubchela from the North Atlantic. 54 records from Anfibios y reptiles de la serranía las Quinchas, Boyacá - Proyecto Boyacá BIO. 5 records from Description of a new species of the Lissochlora albociliaria species group (Lepidoptera: Geometridae, Geometrinae). 2 records from New troglomorphic species of Tomocerus with well-developed postantennal organs (Collembola: Tomoceridae). 9 records from The millipede family Polyxenidae (Diplopoda, Polyxenida) in the faunas of the Crimean Peninsula and Caucasus, with notes on other European Polyxenidae. 158 records from Waldstück Bremerhagen LK Bio Kl. 12. 1 records from Rediscovery of Lestes nigriceps Fraser, 1924 (Odonata: Lestidae) in eastern Cambodia. 15 records from Inventaire des mammifères du Parc de la Haute-Île (93). 96 records from Coleção de Nematoda do Museu Nacional - UFRJ. 232 records from Estimación de la densidad poblacional y dieta del lince (Lynx rufus) Sierra Seri, Sonora y Janos, Chihuahua. 32 records from Stomatopod Crustacea of the Austral and Gambier Islands, French Polynesia. 6652 records from Inventory of plant species through Benin (West Africa). 16 records from (Table 1) PBDE and BDE congener concentration in adipose tissue of East Greenland polar bears collected 1999-2001. 2 records from Two new species of the genus Sinodorcadion Gressitt, 1939 (Coleoptera: Cerambycidae: Lamiinae). 4109 records from South Caribbean Diversity. 1127 records from marine sediment metagenome Metagenome. 719 records from Programme ACT : Répartition Alouette des champs 2012 - 2016 Coordonnées GPS Lambert 93. 2 records from A new species of Aspidura Wagler, 1830 (Squamata: Colubridae: Natricinae) from Sri Pada sanctuary (Peak Wilderness), Sri Lanka. 3752 records from Microbial ecology of archaeal community in sediment from adjacent waters of Rushan Bay. 873 records from Programme ACT : Répartition Grive musicienne 2006 - 2010 Coordonnées GPS Lambert 93. 1966 records from Estudio florístico de los bosques mesófilos de la Sierra Mazateca de Oaxaca, México. 371 records from Bannwald Burghauser Forst. 19 records from The genus Passaloecus Shuckard (Hymenoptera: Crabronidae) from China with four new species and two new records. 948 records from Bulletin du Muséum d'Histoire Naturelle [1895- ]. 486 records from Données du/de la naturaliste Hasrouni Sami provenant de la base de donnée du SINP Île-de-France CETTIA. 290 records from Données 2016 Pélobate brun Comité Départemental de Protection de la Nature et de l'Environnement. 31885 records from Records of Avifauna of Wetlands around Keoladeo National Park, Bharatpur, India. 54 records from Three new goatfishes of the genus Upeneus (Mullidae) from the Indo-Pacific, with a redescription of colour patterns in U. margarethae. 4 records from Three new species of Grotea Cresson (Hymenoptera: Ichneumonidae: Labeninae) from Colombia. 20 records from Revision of the genus Parvimysis (Mysida, Mysidae) with descriptions of five new species from coastal waters of the Caribbean. 13 records from The genus Mecodema Blanchard 1853 (Coleoptera: Carabidae: Broscini) from the North Island, New Zealand. 986 records from HDCF herbarium - Universidade Federal de Santa Maria - Herbário Virtual REFLORA. 10 records from Revision of Lutnes Cameron (Hymenoptera: Eupelmidae). 2127 records from ZUEC-OPH - Coleção de Ophiuroidea do Museu de Zoologia da UNICAMP. 5 records from Redescription of Tapinesthis inermis (Araneae, Oonopidae), with detailed information on its ultrastructure. 18096 records from FBIP:IZIKO-UCT:Historical Invertebrates (1930-1980). 564 records from Atewa Range Forest Reserve Bryophytes dataset, Ghana. 7 records from The publication of primary biological events in the international GBIF (Global Biodiversity Information Facility) network: A case study with a small dataset of field collected occurrence samples of Buriti palms (Mauritia flexuosa).. 4 records from New species of Moluccan trichaline net-winged beetles, with remarks on the phylogenetic position and distribution of Schizotrichalus (Coleoptera: Lycidae: Metriorrhynchinae). 2621 records from Fungi specimens of Saitama Museum of Natural History. 20507 records from University of Guam Insect Collection. 11565 records from National Botanic Garden Belgium - Myxomycetes. 37 records from Naturbelassene ehemalige Wiese am Haselbach (Privates Schutzgebiet). 689 records from Programme ACT : Répartition Pie bavarde 2006 - 2010 Coordonnées GPS Lambert 93. 174 records from Artenvielfalt des "Grünen Klassenzimmers". 3 records from Two new species in the genus Indolipa Emeljanov, 2001 (Hemiptera: Fulgoromorpha: Cixiidae: Pentastirini) from China. 516 records from Museu de Ciències Naturals de Barcelona: BGJBB. 4 records from Taxonomy of ant species (Hymenoptera: Formicidae) collected by pitfall traps from Sinai and Delta region, Egypt.. 36 records from BIOMEO_2017_12_18. 1 records from First record of Orthelimaea himalayana (Ingrisch, 1990) (Orthoptera: Tettigoniidae: Phaneropterinae: Elimaeini) from India with description of its female. 11423 records from Inventario florístico y entomofaunístico en tres objetos de conservación ecosistémicos en las zonas núcleo de las reservas estatales de Balam-kú y Balam-kin, Campeche. 3 records from Holomorphology of Kamimuria peppapiggia sp. n. (Plecoptera: Perlidae) from the foothills of Taihang Mountains, Henan Province of China. 1 records from A new species of Synopeas (Hymenoptera: Platygastridae) parasitizing Pauropsylla cf. depressa (Psylloidea: Triozidae) in India. 1 records from Three new species of the free-living marine nematode Metoncholaimus Filipjev 1918 (Enoplida, Oncholaimidae) from Argentinean coasts. 33 records from (Table 2) Distribution of early late Eocene fossil content in ODP Hole 115-714A. 518 records from Fishes in MZNA-VERT: monitoring program in the Suspiro stream (Spain).. 3 records from A new species of Ninia (Serpentes: Dipsadidae) from Chocó-Magdalena biogeographical province, western Colombia. 11 records from Paracobitis abrishamchiani, a new crested loach from the southern Caspian Sea basin (Teleostei: Nemacheilidae). 4083 records from MCP-Aves - Coleção de Aves. 2 records from Danio htamanthinus (Teleostei: Cyprinidae), a new species of miniature cyprinid fish from the Chindwin River in Myanmar. 1 records from Acromyrmex fowleri: a new inquiline social parasite species of leaf-cutting ants from South America, with a discussion of social parasite biogeography in the Neotropical region. 14 records from Nemertini - SMF. 4 records from Redescription of Seira pallidipes Reuter, 1895 and its synonymization with Seira pillichi Stach, 1930 (Collembola, Entomobryidae, Seirini). 778 records from Bird specimens of Saitama Museum of Natural History. 371 records from orthopteracollections-nhmj-ioj. 1 records from A new species of Microhyla Tschudi, 1838 (Anura: Microhylidae) from West Coast of India: an integrative taxonomic approach. 56 records from New records of ants (Hymenoptera: Formicidae) from Iran.. 65 records from Données du/de la naturaliste Thibault Marie Thérèse provenant de la base de donnée du SINP Île-de-France CETTIA. 25 records from New data on the Syrphidae (Diptera) of Iran, with descriptions of two new species. 1 records from A revision of the Neotropical ant-like genus Cardiacephala Macquart, including Plocoscelus Enderlein syn. nov. (Diptera: Micropezidae, Taeniapterinae). 15 records from Mites of the genus Malaconothrus (Acari: Cryptostigmata) from the British Isles. 27254 records from ARC-PPRI: National Collection of Nematodes and South African Plant-Parasitic Nematode Survey(1901-2014). 7 records from Taxonomy of Morellia Robineau-Desvoidy (Diptera: Muscidae): revision of the subgenera Morellia s. str. and Parapyrellia Townsend. 1 records from Taxonomic contributions to Ageniella Banks, 1912 (Hymenoptera: Pompilidae) from Brazil. 14 records from A review of Scaphisomatini from Sulawesi, with descriptions of ten new species (Coleoptera: Staphylinidae: Scaphidiinae). 5462 records from FloVegSI-FAV - Faunistical database of ZRC SAZU. 2712064 records from SLU Aqua Institute of Freshwater Research National register of survey test-fishing - NORS. 287870 records from Florida Keys Reef Visual Census 2014. 9 records from Troglocoelotes gen. n., a new genus of Coelotinae spiders (Araneae, Agelenidae) from caves in South China. 5 records from Two new species of Brueelia Kéler, 1936 (Ischnocera, Philopteridae) parasitic on Neotropical trogons (Aves, Trogoniformes). 228 records from Bishop's University Insect Collection (BUIC). 18 records from ALTERECO_2017_12_18. 29 records from Caracterización Ecológica de la Fauna del Páramo de Frontino o del Sol. 15554 records from A practical introduction to microbial molecular ecology through the use of iChips. 25 records from Chameleonfishes in Bangladesh: hipshot taxonomy, sibling species, elusive species, and limits of species delimitation (Teleostei: Badidae). 5346 records from Sediment metagenome. 1702 records from BioGIS - Bryophytes - HUJ collections. 2 records from Arthropoda Collection of the Seto Marine Biological Laboratory, Kyoto University. 501785 records from BioFokus. 15255 records from Anymals+plants - Citizen Science Data. 17943 records from Arctic benthic invertebrate collection of the Zoological Institute of the Russian Academy of Science. 1 records from New or little-known taxa of Anurophorinae (Collembola) with anal spines from East Asia with notes on DNA barcode. 957 records from Collection de longicornes et autres coléoptères saproxyliques de Lionel Valladares. 27 records from Additions to Andiorrhinus (Turedrilus) (Rhinodrilidae, Clitellata) from Eastern Amazonia. 991 records from Données du/de la naturaliste CARON Julien provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from New species of Diatrichalus (Coleoptera: Lycidae) from New Guinea and the Moluccas. 45970 records from Herbarium Universitatis Daugavpiliensis. 592 records from Colección de Entomología - Curculionidae. 5156 records from Submarine Ligurian Canyons Water Prokaryotic and Protist Communities. 1571 records from Bryophyte specimens of National Museum of Nature and Science (TNS). 1 records from Three new species of Anacharis Dalman, 1823 (Hymenoptera: Figitidae), with revised taxonomy and distribution records of Palaearctic and Indomalayan species. 2208 records from marine sediment metagenome Raw sequence reads. 13 records from Redescription of two species and five new species of Dispio Hartman, 1951 (Spionidae: Polychaeta) from the eastern Pacific Coast and Caribbean Sea, with a review of the genus. 2 records from Taxonomic additions of Embolemidae and Sclerogibbidae (Hymenoptera: Chrysidoidea) from Japan, with description of a new species of Trogloembolemus. 6 records from Tretogonia Melichar (Hemiptera: Cicadellidae: Proconiini): two new species from South Brazil and a redescription of T. dentalis Emmrich, 1988. 462 records from (Table 1) Abundance of Globigerinoides sacculifer and Globigerinoides ruber and oxygen and carbon stable isotopes of different planktonic foraminifers at DSDP Hole 78-541. 555 records from Colección Zoológica Universidad del Tolima (CZUT) - Arácnidos. 776 records from Programme ACT : Répartition Pie bavarde 2010 - 2014 Coordonnées GPS Lambert 93. 2 records from A new species of Ancistrus Kner, 1854 (Siluriformes: Loricariidae) from rio Madeira basin, Amazonas State, Brazil. 9811 records from Colección, preservación y caracterización de cultivares criollos de origen español de trigo y centeno de México. 6 records from Description of five new species of the genus Stigmaeus Koch (Acari: Raphignathoidea: Stigmaeidae) from Turkey. 19665 records from EDP Baixo Sabor: Land Birds - Construction and Reservoir Filling Phases: stream weirs in the Sabor tributaries [2010-2014]. 1 records from The neotype of Macrostemum hyalinum (Pictet 1836) (Trichoptera: Hydropsychidae) and a key to males of Neotropical species of this genus. 424 records from Collection de C.C.H. Jongkind aux Monts Nimba. 18960 records from Análisis de las relaciones entre las diversidades alfa, beta y gamma a distintos niveles de escala espacial: Procesos históricos y ecológicos que intervienen. V Etapa. 2 records from A taxonomic study of Eupolyphaga Chopard, 1929 (Blattodea: Corydiidae: Corydiinae). 1 records from A new Physoschistura from a Salween affluent in western Yunnan (Teleostei: Nemacheilidae). 6230 records from Plecoptera. 4 records from Taxonomy of the Capensibufo rosei group (Anura: Bufonidae) from South Africa. 44 records from Mamíferos pequeños en el municipio de Medina, Cundinamarca - Proyecto Colombia Bio. 2 records from A new species of Trismegistomya Reinhard (Diptera: Tachinidae) from Area de Conservacion Guanacaste in northwestern Costa Rica. 8 records from A revision of the subgenus Eurycercus (Teretifrons) Frey, 1975 (Crustacea: Cladocera) in the Holarctic with description of a new species from Russian Arctic. 817 records from Programme ACT : Répartition Tourterelle turque 1997 - 2001 Coordonnées GPS Lambert 93. 5 records from New species of Protosticta Selys from Vietnam with a key to the males of the P. curiosa group (Odonata: Platystictidae). 8 records from A review of the ant genus Metapone Forel from Madagascar.. 9 records from Diversity of Sternaspidae (Annelida: Terebellida) in the South China Sea, with descriptions of four new species. 184 records from New taxa and records of Gryllacrididae (Orthoptera, Stenopelmatoidea) from South East Asia and New Guinea with a key to the genera. 12 records from New findings on the Neotropical species Hermetia goncalvensi Albuquerque, 1955 (Diptera: Stratiomyidae): redescription, puparium, and geographical records. 1508 records from SPC PROCFish/C Invertebrates Observations Solomon Islands 2006. 2834 records from Northern Gulf of Mexico Hypoxia can Alter Sediment Communities of Nitrifying Archaea. 29559 records from Occurrences de vecteurs de maladies recensées à l'Hôpital de Mènontin. 38 records from Numbers and statistics of benthic foraminiferal Q-mode assemblages for the Lower Oligocene of section Poetschbichl in the Lower Inn Valley area. 1 records from Review of continental North and Central American Paracloeodes Day 1955 (Ephemeroptera: Baetidae), including description of a new species from Minnesota, U. S. A.. 15 records from Hessen-GEO-Tag am Schlossberg von Homberg/Efze. 2120 records from Flora vascular acuática de la cuenca del Río Tamesí. 717 records from Programme ACT : Répartition Faisan commun 2008 - 2012 Coordonnées GPS Lambert 93. 3 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Algae. 10160 records from North East Scotland Terrestrial Mammals 1900-2017 (excluding squirrels, wild cats and marine mammals). 12 records from A new genus and two new species of miniature clingfishes from temperate southern Australia (Teleostei, Gobiesocidae). 20 records from On the genus Systaria (Araneae: Clubionidae) in Southeast Asia: new species from caves and forests. 120 records from BIRDRACE The early birds. 1 records from Two new goatfishes of the genus Upeneus (Mullidae) from Australia and Indonesia. 462 records from Données odonates collectées par le CEN Aquitaine entre 1995 et 2015. 5 records from Two new nematode species of the genus Tobrilus Andrássy, 1959 (Nematoda, Triplonchida) from Lake Baikal, Russia. 69 records from Ours 2010 présence Occasionnelle Mailles 10km LAEA Réseau Ours brun ONCFS. 17 records from A checklist of epibiont suctorian and peritrich ciliates (Ciliophora) on halacarid and hydrachnid mites (Acari: Halacaridae & Hydrachnidia). 8737 records from Andes to Amazon Biodiversity Program. 702 records from Echigo-Matsunoyama Museum of Natural Science, Usuke Shiga butterfly collection. 1096 records from Données naturalistes de Stéphane ORIO. 439 records from Collection Echinodermata - ZMB. 60 records from Suivi botanique et entomologique pour la gestion de la portée de RTE sur l'emprise de la RNN de Bassée. 403 records from Inventario herpetofaunístico del noroeste de Hidalgo. 243 records from WildesMoor bei Schwabstedt. 435 records from The Paleontological Collections at the Bayerische Staatssammlung für Paläontologie und Geologie. 32 records from Antarctic Pycnogonids II. 59788 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 3 records from Three new species of jumping spiders of the genus Hypaeus Simon, 1900 from Colombia (Salticidae: Salticinae: Amycini). 10 records from Oberservation of birds at station PS14/143 along 49° West. 1763 records from Herpetofauna de la región marina prioritaria Corredor Puerto Madero, Chiapas, México. 9366 records from ZooplanktonBeaufortSeaNOGAP2. 10 records from More than just the number of denticles: morphometric and limb variability in Neotropical cladoceran Alonella dadayi (Crustacea: Cladocera: Chydoridae). 7920 records from Sinfonevada: Dataset of Floristic diversity in Sierra Nevada forest (SE Spain). 212 records from Données des naturalistes POHIER et LEFORT provenant de la base de donnée du SINP Île-de-France CETTIA. 7 records from Update of the genus Leptochiton (Mollusca: Polyplacophora) in Chilean deep waters: three new reports and description of two new species. 2560 records from Upper Silesian Museum, Bird Observations. 192 records from Briófitos del cerro Tacarcuna-Chocó, en el marco del proyecto Colombia BIO 2017. 1168 records from Données naturalistes de Quentin ROME. 1386 records from Aves de fragmentos de Bosque seco en la región del Caribe Colombiano. 13 records from Suivi de la reproduction des Lamproies de Planer sur les sites Natura 2000 en Seine-et-Marne. 1 records from New Lepidocyrtus Bourlet, 1839 from riverine woodland in Hungary (Collembola, Entomobryidae). 4 records from Taxonomic notes on Chinese Lamiini (Coleoptera: Cerambycidae: Lamiinae). 855 records from Insectos recolectados en trampas Malaise en el departamento de Santander - Proyecto Colombia Bio. 2189 records from Jardín Botánico Atlántico, Gijón: JBAG. 539 records from étude entomologique de la ZSC du Bois de Vaires. 125623 records from The Himalayan Uplands Plant database (HUP Version 1). 1 records from Description of a new species of the Ponerine ant genus, Emeyopone (Hymenoptera: Formicidae) from Karnataka, India.. 130 records from Artenvielfalt auf dem Schulgelände. 358 records from Données rhopalocères collectées par le CEN Aquitaine entre 1970 et 2015. 349 records from DREAL_PACA_-_N2000_-_GIP_Calanques_2017_12_18. 72 records from Données sur les Opisthobranches et Planaires de Mayotte. 1 records from A new species of Rock Gecko of the genus Cnemaspis Strauch, 1887 (Squamata: Gekkonidae) from Belitung Island, Indonesia. 6528 records from National Museum of Natural Science. 419 records from A survey of the weevils of Ukraine (Coleoptera: Curculionoidea). 165 records from Diversidad de anfibios en tres coberturas vegetales y su relación con actividades antrópicas (amenazas) presentes en el Parque Nacional Natural Tatamá y su área de influencia.. 11 records from (Table 2) Population density and zoobenthos biomass in bottom communities of the Novosibirsk Polynya in September 2008. 105 records from Fish Fauna of Berlin. 484 records from Agencement temporel des populations et des peuplements d'invertébrés benthiques. 4 records from Not endemic after all: Imparipecten Freeman, 1961 (Diptera: Chironomidae) described from the Neotropical Region. 3775 records from Données naturalistes de Charlotte PICARD. 2 records from A revision of the South American species of the ant genus Probolomyrmex (Hymenoptera: Formicidae).. 2 records from The genus Sinodiaptera Dellacasa (Coleoptera: Scarabaeidae: Aphodiinae) in Taiwan. 625 records from Mycology collection, Norwegian Forest and Landscape Institute. 17 records from Amazoonops, a new genus of goblin spiders (Araneae: Oonopidae) from the Brazilian Amazon. 2 records from Amphibian specimens of Obihiro Centennial City Museum. 3 records from Porphyrocrinus daniellalevyae n. sp. (Echinodermata: Crinoidea), a sea lily from the tropical western Atlantic with a unique crown pattern. 42 records from Inventaire des Octocoralliaires des fonds sédimentaires de la région niçoise. 6 records from A new species of the genus Bertholdia Schaus, 1896 (Lepidoptera: Erebidae: Arctiinae) from the Neotropical region: Bertholdia zoenia sp. n.. 131 records from University of Graz, Institute of Plant Sciences - Herbarium GZU. 34 records from Revision of the Australian Union-Jack wolf spiders, genus Tasmanicosa (Araneae, Lycosidae, Lycosinae). 35 records from New distribution data for some charismatic tramp species of Platygastroidea (Hymenoptera). 11840 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2015. 3 records from A new species of Rhabdops Boulenger, 1893 (Serpentes: Natricinae) from the northern Western Ghats region of India. 1 records from Pentatomiana beckerae gen. nov. and sp. nov., a new Neotropical Pentatomini (Hemiptera, Heteroptera, Pentatomidae). 30 records from Occurrence data of Anasillomos (Diptera: Asiloidea: Asilidae). 1942 records from Collection ornithologique A. Maës. 1 records from Stylogomphus thongphaphumensis (Odonata: Anisoptera: Gomphidae), a new gomphid dragonfly and the first record of S. malayanus Sasamoto, 2001 from Thailand. 1 records from Libnotes crane flies (Diptera: Limoniidae) from Jeju Island (South Korea). 926 records from Determinación del estado actual de cinco especies de cactáceas amenazadas del estado de Tamaulipas, México. 4 records from Minooa Yamanaka, 1996, a genus newly recorded to China with description of a new species (Lepidoptera, Pyralidae, Pyralinae). 5300 records from Actualización de la base de datos de diversidad taxonómica de las larvas de peces de Bahía Vizcaíno. 46 records from Mammal specimens of Komatsu City Museum. 2 records from A new black fly species of Simulium (Gomphostilbia) (Diptera: Simuliidae) from Sulawesi, Indonesia. 11 records from Urban Barcode Project - Fungi. 7 records from Three new species of Cladorhiza (Demospongiae, Poecilosclerida, Cladorhizidae) from the Northeast Pacific Ocean. 1 records from A new species of Philorhizus Hope, 1838 from Greece (Coleoptera, Carabidae, Lebiini). 12 records from Occurrences de Bouquetin ibérique (Capra pyrenaica) collectées par le PNP et le PNRPA. 5 records from New species and new geographical record of Ochrotrichia Mosely 1934 (Trichoptera: Hydroptilidae) from Rio de Janeiro state, Brazil. 2 records from Swedish Malaise Trap Project (SMTP) - Sphecidae (s lat). 41 records from Örtzemündung (Stedden). 2451 records from Macrobenthos Chukchi Sea, 1986. 1 records from The genus Acantholyda (Hymenoptera, Pamphiliidae) of Japan: A revised key and a description of the previously unknown female of Acantholyda flaviventris. 181 records from Inventory of natural and agroforestry stands characterized by Xylopia aethiopica (Dunal) A. Rich. (south-Benin). 586 records from Inventario taxonómico de los hongos conidales saprobios del parque Yumka' en Villahermosa, Tabasco. 1989 records from (Figure 2) Occurrence of planktonic foraminifers and other selected constituents in samples from DSDP Hole 80-548. 9 records from Proctolaelaps species (Acari: Mesostigmata: Melicharidae) from Egypt, with description of a new species and complementary descriptions of other five species. 2931018 records from Eremaea. 1156 records from Legume Collections of the Plant Genetic Resources Research Institute (CSIR-PGRRI),Ghana. 4739 records from Comparative study in validity of three regions of 18S-rRNA for eukaryote amplicon sequence analyses. 78 records from Marine Offshore Seabed Survey data held by JNCC. 4 records from Two new species of Mendozellus Linnavuori (Hemiptera: Cicadellidae: Deltocephalinae: Deltocephalini) with redescription of Mendozellus asunctia Cheng. 181 records from Análisis del ictioplancton del ecosistema costero de Celestún, Yucatán, México. 15 records from Tardigrad collection of the National Museum of Nature and Science. 3 records from Morphological and molecular evidence for a new species of the genus Panolis Hübner, [1821] (Lepidoptera: Noctuidae). 2 records from Another unusual new gorgonian (Anthozoa: Octocorallia: Plexauridae) from the Aleutian Islands of Alaska. 319 records from Données naturalistes de Monsieur LEFEBVRE François. 1475 records from Digitization of plant specimens from Rhoen and Vogelsberg (FLAD). 3 records from Distribución histórica, prospección actual y áreas potenciales para reintroducir lobo mexicano (Canis lupus baileyi) en Durango, sur de la Sierra Madre Occidental, México. 17301 records from Microbial community in marine sediments. 1230 records from Données du naturaliste Marquet Jacques provenant de la base de donnée du SINP Île-de-France CETTIA. 18 records from Naturtag. 45 records from données espèces - Expertise IPE 63. 1 records from Description of Sweltsa tibetensis sp. n. (Plecoptera: Chloroperlidae) from Tibet Autonomous Region of China. 8 records from Austrolebias ephemerus (Cyprinodontiformes: Rivulidae), a new annual fish from the upper Rio Paraguai basin, Brazilian Chaco. 65 records from Occurrence of mammalia relicts at site Sütto_6. 16071 records from Herbier Louis-Marie (QFA) - Collection de lichens. 2 records from Redescription of Admete sadko Gorbunov, 1946 (Gastropoda: Cancellariidae). 2 records from A new species of Traverella Edmunds, 1948 (Ephemeroptera: Leptophlebiidae) from Brazil. 2 records from Description of two new species and phylogenetic reassessment of Perelleschus O’Brien & Wibmer, 1986 (Coleoptera: Curculionidae), with a complete taxonomic concept history of Perelleschus sec. Franz & Cardona-Duque, 2013. 96508 records from Herbarium of Taiwan Forestry Research Institute. 160408 records from Oiseaux nicheurs de France métropolitaine 2009-2012 - Nidification probable. 3 records from Garra fluviatilis, a new hillstream fish species (Cypriniformes: Cyprinidae) from the Kwai Noi River system, Mae Khlong basin, Thailand. 2 records from New Notophthiracarus species (Acarina, Oribatida, Phthiracaridae) and overview of the distribution of the genus in South Africa. 23 records from Ackerrain Plönhagen. 7019 records from Flora del Valle de Tehuacán-Cuicatlán: III fase. 1 records from Great Sippewissett Marsh Plot nirS Targeted Locus. 1004 records from Données odonates. 242 records from Malawi-Histeridae-Biodiversity-Data. 3 records from Bees of the Hemihalictus series of Lasioglossum Curtis (Hymenoptera, Halictidae) in South Korea. 4 records from New species of Dispio Hartman, 1951 and Streblospio Webster, 1879 (Polychaeta, Spionidae) from the coast of the Iberian Peninsula. 14 records from New species and records of the genus Syllis Savigny in Lamarck, 1818 (Annelida: Syllidae) from Socotra Archipelago (Indian Ocean). 11 records from Taxonomy of widespread Neotropical species of Podisus Herrich-Schäffer (Hemiptera: Pentatomidae: Asopinae): redescription of P. distinctus (Stål, 1860) and revalidation of P. fuscescens (Dallas, 1851). 4439 records from Occurrence data set of Non-Timber Forest Products species for medicinal purposes in Zimbabwe’s biodiversity hotspots. 25 records from New species of subterranean and endogean terrestrial isopods (Crustacea, Oniscidea) from Tuscany (central Italy). 2 records from First record of the family Bolitophilidae (Diptera: Sciaroidea) from the Lagunas de Zempoala National Park, Mexico, with description a new species. 3 records from Freies Projekt Speichersdorf - Region Oberfranken. 3 records from A new species of Ledoyerella, L. kunensis sp. nov. (Amphipoda, Senticaudata, Kamakidae) from South West Africa. 1551 records from (Table 1) Range chart for planktonic foraminifers from ODP Hole 111-667A. 2 records from Updated information on genus Gomphidictinus (Odonata: Gomphidae) in China with description of Gomphidictinus tongi sp. nov.. 6 records from Swedish Malaise Trap Project (SMTP) - Dermaptera. 1 records from Schistura alboguttata, a new loach species of the family Nemacheilidae (Pisces: Cypriniformes) from the Pearl River basin in Guangxi, South China. 774 records from Biodiversidad ictica de la Isla Cayo Serranilla Expedición Seaflower 2017 proyecto Colombia BIO. 7283 records from Colecção Entomológica IIA. 2 records from Teretamon spelaeum, a new species of freshwater crab (Crustacea: Decapoda: Potamidae) from a limestone cave in Meghalaya, India. 313 records from BIRDRACE Gätkes Erben. 6702 records from Antarctic Amphipod Crustaceans: Ant'Phipoda Database (BIANZO). 13 records from The genus Semicerura (Collembola; Isotomidae) in Asia. 17294 records from The cryptogamy collection (PC) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 103 records from There and back again: More on the taxonomy of the crab spiders genus Epicadus (Thomisidae: Stephanopinae). 193 records from EDP Foz Tua Otter (Lutra lutra) [transects] - Ecological Monitoring Program (2011-17). 1900 records from Carabidae of the European North-East of Russia. 5583 records from Actualización y depuración de las bases de datos de la Colección Nacional de Helmintos: P085 y Q028. 1297 records from Recensement et distribution Mammifères marins Guadeloupe Antilles françaises (AET). 7 records from Two new species of the bamboo-feeding planthopper genus Neobelocera Ding & Yang, 1986 from China (Hemiptera, Fulgoroidea, Delphacidae). 4011 records from Consolidación de la colección de referencia de peces de la Estación Mazatlán, (ICMyL-UNAM) e implementación de los mecanismos para su manejo y consulta. 272 records from Inventaire malacologique des murs restaurés en pierre sèche en lien avec l'association "une pierre sur l'autre". 75 records from Banco de Semillas de Boyacá. 262 records from Variability of benthic Foraminifera north and south of the Denmark Strait. 1040 records from Données de l'Association naturaliste d'étude et de protection des écosystèmes CAUDALIS 2015 Chiroptères, Maculinea, Cistude d'Europe. 930 records from DMNS Egg Collection (Arctos). 2225 records from Données naturalistes d'Anaïs MAS. 2538 records from (Table 2) Nannofossil occurrence in ODP Hole 101-627B. 1 records from New records of family Hormathiidae (Cnidaria: Actiniaria) from Brazilian coast with description of Paraphelliactis labiata n. sp.. 13203 records from Lepidopterous specimens of Yamagata Prefectural Museum. 662 records from Alterra (NL) - Microarthropods inventory in grassland and arable land. 1 records from Description of the mature larva and pupa of Ora semibrunnea Pic (Coleoptera: Scirtidae) with notes on its biology. 8 records from The Myriapoda & Onychophora collection (MY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 131 records from Manejo campesino sustentable del maguey papalote del Chilapan. Fase II. 467748 records from DNV GL Sleipner. 3 records from Edwardsya, a new genus of jumping spiders from South America (Araneae: Salticidae: Freyina). 232 records from Inventaire avifaune. 8004 records from University of California Santa Barbara Invertebrate Zoology Collection. 15161982 records from iNaturalist Research-grade Observations. 76 records from Données du/de la naturaliste D'HINZELIN MARCEL provenant de la base de donnée du SINP Île-de-France CETTIA. 65 records from Cuxhaven Schlosspark, Klasse 5e- Amandus-Abendroth-Gymnasium. 3 records from Two new species of the genus Cataglyphis Foerster, 1850 (Hymenoptera: Formicidae) from Iran.. 2 records from Neue Milbenarten aus Kärnten. 1 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 96 records from Anfibios y reptiles de la desembocadura del caño Teracay en el río Tomo, Puerto Carreño, Vichada - Proyecto Colombia Bio. 1820 records from (Figure 10) Range chart of selected dinocysts and acritarchs of ODP Hole 104-644B. 17 records from Synopsis of world Discleroderma Kieffer (Hymenoptera, Bethylidae). 2 records from Description of Penia mantillerii sp. nov. (Coleoptera: Elateridae: Dimini), with a key to Penia species from Vietnam and nearby areas. 2 records from A review species of the genus Ceroplastes (Hemiptera: Coccomorpha: Coccidae) in China. 390 records from Entomology Collection at the Natural History Museum of Utah. 31 records from Superórden Dictyoptera del Museo de Entomología de la Universidad del Valle (Cali, Colombia). 64 records from Lynx 1996 présence Occasionnelle Mailles 10km Réseau Loup-Lynx ONCFS. 5397 records from Colección de Fabales del Museo Botánico CORD - IMBIV. 1 records from Cladistic analysis and synopsis of Chloropepla Stål (Hemiptera: Heteroptera: Pentatomidae) with the description of three new species. 169717 records from Locations of plants on dot distribution maps in the Flora of Siberia (Flora Sibiraea, 1987–1997). 85153 records from ALCB - Herbário Alexandre Leal Costa. 114 records from BIRDRACE LiLaLau. 9 records from Herbarium specimens of Limoges university (LIMO). 17 records from Comunidad de Herpetos presentes en el río Tutunendo, Municipio de Quibdó-Chocó. 3750 records from Biobanco de ADN Vegetal de la Universidad de Salamanca: SALA-DNA. 6 records from To the knowledge of Oriental species of subgenus Pseudochlaeniellus Jeannel, 1949 (Coleoptera, Carabidae, Chlaenius). 79214 records from Fish specimens of Kagoshima University Museum. 3764 records from UTEP Invertebrates (Arctos). 112 records from Revision of the crab-spiders of the genus Runcinioides Mello-Leitão, 1929 (Araneae, Thomisidae). 217 records from Inventaire des odonates 2014. 59 records from Schulteich Freie Waldorfschule Darmstadt. 7 records from Coeliccia rolandorum sp. nov. from eastern Cambodia and southern Vietnam, the eastern relative of C. kazukoae Asahina, 1984 (Odonata: Platycnemididae). 10 records from A new genus of ground and litter-dwelling pholcine spiders from Sarawak (Araneae, Pholcidae). 2 records from Molecular phylogeny of Hiptage (Malpighiaceae) reveals a new species from Southwest China. 629 records from Inventario de Flora de la Reserva Forestal Protectora Regional Cuchillas del Tigre, El Calón y La Osa. Municipios de San Francisco y Sonsón-Antioquia.. 10 records from Electrogena brulini sp. nov. and E. vipavensis Zurwerra & Tomka, 1986 syn. nov. revealed by integrative taxonomy of E. gridellii (Grandi, 1953) (Ephemeroptera: Heptageniidae). 8 records from Five new species of the Acantholycosa - complex (Araneae: Lycosidae) from Mongolia. 611 records from Données du Râle gris sur le territoire de la Guadeloupe. 2 records from Odontamblyopus rebecca, a new species of amblyopine goby from Vietnam with a key to known species of the genus (Gobiidae: Amblyopinae).. 33 records from Four new Amynthas and Metaphire earthworm species from nine provinces in southern China. 292 records from Monitoreo y recolección de la diversidad de razas de maíz criollo en la región de la Huasteca en México para complementar las colecciones de los Bancos de germoplasma de INIFAP y CIMMYT. 994 records from Amphipoda Hyperiidea of the Southern Ocean: catalogue and occurrences. 12 records from New records of the larval forms Cerataspis monstrosa and Amphionides reynaudii (Crustacea: Decapoda) from the western tropical Atlantic. 688 records from données arachnologiques de CARR David. 145 records from Foto trampeo al interior de las áreas del Banco de Hábitat del Meta de Terrasos. 1135 records from MarineGEO visual diver surveys of fish communities around Carrie Bow Cay, Belize, 2015. 9 records from A new species of the genus Verilus (Teleostei, Percomorpha, Acropomatidae) from Brazil. 1303 records from Flora útil del Municipio de la Huerta, Jalisco. 11 records from Ensemble des données Odonates. 2 records from Nandus prolixus, a new species of leaf fish from northeastern Borneo (Teleostei: Perciformes: Nandidae).. 884 records from Diversité et distribution de quelques espèces de plantes agroforestières au Bénin. 1 records from A new Liopeltis Fitzinger, 1843 (Squamata: Colubridae) from Pulau Tioman, Peninsular Malaysia. 477 records from Coleção de Ictiologia do Museu de Ciências Naturais da Universidade do Vale do Taquari - Univates (ZIUMCN-UNIVATES). 3 records from Psychotria niauensis sp. nov. (Rubiaceae), espèce calcicole endémique de la Polynésie française, décrite de l’atoll soulevé de Niau (Tuamotu). 1725 records from Inventario y monitoreo del Canal de Infiernillo para el comanejo de los recursos marinos en el territorio Seri, Golfo de California. 5401 records from Données Lépidoptères de l'Auvergne transmises par Pascal Peyrache.. 990 records from Bacterial communities from Thrombolites of Lake Sarmiento. 20 records from Description of five new Wulfila (Araneae, Anyphaenidae) species from Mexico with comments on the taxonomy of the genus. 25068 records from La colección briológica del Herbario Nacional (MEXU). Actualización 2000. 134 records from BIRDRACE Griffin Wood Warblers. 261 records from Données espèces -expertise IQE 3. 2170 records from Modelos predictivos de distribución geográfica para Spizella wortheni, Cynomys mexicanus, Vulpes macrotis zinseri y Taxidea taxus berlandieri. 1422 records from Données du/de la naturaliste Chevreau David provenant de la base de donnée du SINP Île-de-France CETTIA. 10 records from Description of two new species of Regalana and a new genus of Gyponini (Hemiptera: Cicadellidade: Iassinae). 5 records from Taxonomic study of the genus Promalactis Meyrick, 1908 (Lepidoptera: Oecophoridae) VIII. The densimacularis species group, with descriptions of four new species. 4 records from Review of the genus Holostaspis Kolenati, 1858 (Acari: Laelapidae). 4 records from A new species and two new records of the ground spider genus Apopyllus (Araneae, Gnaphosidae) from Paraguay. 1 records from Review of the genus Haba Semenov, 1954 (Hymenoptera Chrysididae) with the key to species. 38 records from Ours 2006 présence Occasionnelle Mailles 10km LAEA Réseau Ours brun ONCFS. 12 records from Art´n Vielfalt im Kinderwald. 47 records from Asturodes Amsel (Lepidoptera: Crambidae: Spilomelinae): Three New Species From The Western Hemisphere And Food Plant Records From Area De Conservación Guanacaste, Costa Rica. 432 records from Fishes in MZNA-VERT: ecological assessment of the Guadalope river in Aliaga (Spain). 48 records from Herpetofauna de la expedición Pisba - Proyecto Boyacá BIO UPTC. 14 records from Taxonomic study of the genus Fujimacia Marumo, 1939 (Lepidoptera: Pyralidae) in China, with descriptions of four new species. 548 records from Naturalis Biodiversity Center (NL) - Crustacea. 5 records from A new species of Victrix Staudinger, 1879 from Kazakhstan (Lepidoptera, Noctuidae). 60 records from Amphibian and Reptilian (KIEE-AR). 21 records from Brown algae specimens of Komatsu City Museum. 232 records from Filogenia de las cactáceas columnares (Pachycereeae) con base en caracteres anatómico-morfológicos. 360 records from Données du naturaliste Arnaud Bak. 5919 records from Catálogo taxonómico y biogeográfico de los radiolarios (orden Polycystina) de la región central y sur del Golfo de California. 2 records from A new pea crab species of the genus Arcotheres Manning, 1993 (Crustacea: Decapoda: Brachyura: Pinnotheridae) from India. 12 records from (Table 1) Sex, age and numbers of polar bear skulls (Ursus maritimus) collected in Svalbard. 420 records from (Table 2) Distribution of calcareous nannoplankton in selected samples of ODP Site 112-679. 2 records from Données de Lépidoptères de Bruno DAUGET - Dépt des PYRENEES-ORIENTALES (66). 138 records from Georgia Southern University - Savannah Science Museum Herpetology Collection. 1044940 records from CLICNAT Base de données naturaliste picarde gérée par Picardie Nature. 413272 records from DATAVES. 3450 records from University of Tennessee Bryophyte Herbarium. 23 records from Herpetofauna asociada a la cuenca del río Quito - Chocó, 2014. 313 records from DATABASE OF FINDS OF RARE LICHEN SPECIES Lobaria pulmonaria IN RUSSIA. 5389 records from University of Alberta Museum of Zoology Ichthyology Collection (UAMZ). 2 records from Taxonomic Studies on the Genus Myrmoteras Forel (Hymenoptera: Formicidae), with Description of Two New Species from India. 490 records from Sequences obtained from two sponge genera (Hyrtios, Aiolochroia), one zoanthid (Palythoa), and marine sediments. Metagenome. 721 records from The Broward College Insect Collection. 742 records from Composición y estructura de la ornitofauna de la reserva de la biósfera Pantanos de Centla. 179 records from The female velvet ants (aka modkhong) of southern Thailand (Hymenoptera: Mutillidae), with a key to the genera of southeast Asia. 42 records from SuLaMa reptile survey 2013. 2 records from Description of a new species of Willemia (Collembola: Hypogastruridae) from Panama with key to Willemia species occurring in the Americas. 14 records from Berea College, Ralph L. Thompson Herbarium. 3224 records from Amphibiens de Guyane. 9653 records from Ecosphère_2017_12_18. 9 records from Revalidation of Pterinopelma Pocock 1901 with description of a new species and the female of Pterinopelma vitiosum (Keyserling 1891) (Araneae: Theraphosidae: Theraphosinae). 512 records from Análisis de la biodiversidad y servicios ecosistémicos para su aplicación en la toma de decisiones en el departamento de Boyacá/Boyacá Bio-Flora El Consuelo. 11 records from First records of two flower bug genera from Myanmar (Hemiptera: Heteroptera: Anthocoridae: Anthocorinae: Oriini), with description of a new species of Bilia. 38 records from BB-Biodiversität a. 4 records from Collection Myriapoda - SNSD. 80308 records from Actualización y enriquecimiento de las bases de datos del proyecto de evaluación y análisis geográfico de la diversidad faunística de Chiapas. 1 records from First Record of the Ceratioid Anglerfish Species Gigantactis microdontis (Teleostei: Lophiiformes: Gigantactinidae) in the Western Pacific Ocean. 17 records from Marine metagenome ICM_AGW. 25 records from Two new species of the scorpionfish genus Trachyscorpia (Sebastidae: Sebastolobinae) from the southern Indo-West Pacific, with comments on the distribution of T. eschmeyeri.. 4 records from A new species of Megatibicen endemic to Mescalero-Monahans shinnery sands (Hemiptera: Auchenorrhyncha: Cicadidae). 905 records from Weber State University Herbarium. 4 records from Survey of sand flies (Diptera: Psychodidae: Phlebotominae) in Guajará-Mirim State Park forest reserve, near the Brazil-Bolivian border, with a description of Pintomyia fiocruzi, a new sand fly species. 384 records from Marine metagenome ICM_AWP. 3580 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 4 records from Delimitation and description of three new species of Himalopsyche (Trichoptera: Rhyacophilidae) from the Hengduan Mountains, China. 2 records from (Table 7) Percent distribution of calcareous nannofossils at ODP Hole 125-786A. 2 records from A new species of Cyrtodactylus (Squamata: Gekkonidae) and the first record of C. otai from Son La Province, Vietnam. 1655 records from Collections of Bioclass, school #179, Moscow. 6 records from Two new species of the conger eel genus Bathycongrus (Anguilliformes: Congridae) from Taiwan. 21809 records from Microbial community structure and dynamics in the oxygen minimum zone of the Northeast subarctic Pacific Ocean. 69 records from Global Ocean Sampling Expedition. 5 records from Five new species of the spider genus Pholcus Walckenaer, 1805 (Araneae: Pholcidae) from China and Thailand. 6 records from Two new species of the spider genus Wanniyala Huber & Benjamin, 2005 (Araneae Pholcidae) from Sri Lanka. 69 records from BIRDRACE Pfeifenten. 11 records from Ephemeroptera Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 5335 records from Marine metagenome ICM_JRV. 42 records from The Pygopleurus Motschulsky (Coleoptera: Scarabaeoidea: Glaphyridae) of mainland Greece: taxonomy, faunistics and ecological notes. 224 records from Kherson State University herbarium (KHER), Department of Botany. 146 records from Données de la naturaliste Laurence Beauchamp. 1945 records from Inventaire des Coléoptères Longicornes des Antilles françaises. 52 records from Collections ichtyologiques et herpétologiques (BOUM). 6611 records from Nijmegen Natural History Museum (NL) - Herbarium. 3 records from Two new species of amphipods (Crustacea: Amphipoda: Photidae) from Korean waters with a redescription of Gammaropsis longipropodi. 751 records from Programme ACT : Répartition Pie bavarde 2007 - 2011 Coordonnées GPS Lambert 93. 13709 records from Données naturalistes de Bruno OGER. 11906 records from Colección de mariposas del Museo de Entomología de la Universidad del Valle. 1 records from Ta xonomic study on the Chinese Steninae (Coleoptera, Staphylinidae), with descriptions of three new species of the Genus Stenus Latreille. 124922 records from DEEPEND: Microbiome and bacterioplankton rRNA gene sequence data collected from Gulf of Mexico seawater samples. Cruises DP03 and DP04 from Jan 2016 - December 2016. 18 records from Five new species and novel descriptions of opposed sexes of four species of the spider genus Attacobius (Araneae: Corinnidae). 83 records from Données du/de la naturaliste Swoszowski Florie provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from Sarcocheilichthys vittatus, a new species of gudgeon (Teleostei: Cyprinidae) from the Poyang Lake Basin in Jiangxi Province, South China. 71 records from Occurrence of mammalia relicts at site Pestera Bursucilor. 957 records from Département_du_Var_2017_12_18. 10 records from Occurrence of mammalia relicts at site Salzgitter-Lebenstedt. 191 records from sediment microorganism Metagenome. 807 records from Aquatic Insects from the Caatinga: checklists and diversity assessments of Ubajara (Ceará State) and Sete Cidades (Piauí State) National Parks, Northeastern Brazil. 69 records from Revision of the squat lobsters of the genus Leiogalathea Baba, 1969 (Crustacea, Decapoda, Munidopsidae) with the description of 15 new species. 300 records from Marine sediment metagenome ICM_GMS. 3 records from Tropiorhynchus annandalei (Coleoptera: Scarabaeidae: Rutelinae), a new species from Maharashtra, India. 1962 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Entomology National Collection (MACNEn). 2 records from Description of a new snake eel Ophichthus olivaceus (Teleostei: Anguilliformes Ophichthidae) from the Red Sea. 609 records from Arácnidos - Miriápodos de la expedición al Río Apaporis - Proyecto Colombia BIO. 3455 records from permafrost metagenome Targeted loci environmental. 1 records from Review of the genus Paradonus Stibick, 1971 (Elateridae: Negastriinae), with three new North American species. 41050 records from University of Alberta Vascular Plant Herbarium (ALTA-VP). 4 records from Moriphila furva gen. and sp. nov. (Hemiptera: Psylloidea: Homotomidae), a new jumping plant-louse from Korea associated with Morus australis (Moraceae). 139 records from A new western Canadian record of Epeoloides pilosulus (Cresson). 4837 records from Free-living marine Nematodes from San Antonio and Cormoranes sandy beaches (Rio Negro, Argentina), 2006.. 3137 records from CTD water column metabarcoding. 1101 records from A species-level taxonomic review and host associations of Glyptapanteles (Hymenoptera, Braconidae, Microgastrinae) with an emphasis on 136 new reared species from Costa Rica and Ecuador. 57913 records from Fichier communal des ongulés. 5 records from Sächsische Schweiz (Pfaffenstein). 2 records from Two new species of Petrobunus from China (Opiliones: Laniatores: Petrobunidae). 564 records from Conservación de la tortuga caguama del Pacífico (Caretta caretta): protección dentro del hábitat crítico de alimentación y desarrollo en Baja California Sur. 5 records from Revision of Tomocerus similis Chen & Ma, with discussion of the kinoshitai complex and the distal tibiotarsal chaetae in Tomocerinae (Collembola, Tomoceridae). 1880 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Vascular Plants National Collection (BAv). 25 records from Small, rare and little known: new records and species of Cardiomya (Bivalvia: Cuspidariidae) from Brazil. 28 records from Two new genera and five new species of Mugadina - like small grass cicadas (Hemiptera: Cicadidae: Cicadettini) from Central and Eastern Australia: comparative morphology, songs, behaviour and distributions. 9176 records from Réseau de surveillance Polynesia Mana - Peuplements de poissons. 6 records from New species of grasshopper genus Aptoceras Bruner, 1908 (Orthoptera, Acrididae, Ommatolampidinae, Ommtolampidiini) from Iguaçu National Park (Southern Brazil), including a taxonomic key and distribution data. 63 records from Lynx 2009 présence Régulière Mailles 10km Réseau Loup-Lynx ONCFS. 115 records from Living Cirripedia. 261 records from Annales de la Société entomologique de France [1832- ]. 7 records from Review of the genus Amemboides Polhemus & Andersen, 1984 (Hemiptera: Heteroptera: Gerridae) from China, with description of a new species. 68 records from Type specimens in the Port Elizabeth Museum, South Africa, including the historically important Albany Museum collection. Part 2: Reptiles (Squamata). 2 records from Zur Oribatidenfauna des Leopoldsberges von Wien (1. Beitrag). 1 records from Madangella altirostris, a new genus and species of palaemonid shrimps (Crustacea: Decapoda: Palaemonidae) from Papua New Guinea. 1016 records from ConDidact Citizen Science Surveys - Spiders 2011. 2 records from Lemyra persephone, a new autumnal species from Yunnan, southwestern China (Lepidoptera, Erebidae, Arctiinae). 3428 records from Macroinvertebrados y perifiton pertenecientes a cuatro regiones de Colombia. 2 records from Four new species of Magelona (Annelida: Magelonidae) from Easter Island, Guam and Hawaii. 16 records from A new western Canadian record of Epeoloides pilosulus (Cresson), with discussion of ecological associations, distribution and conservation status in Canada. 1 records from Taxonomy and phylogeny of calcareous sponges (Porifera: Calcarea: Calcinea) from Brazilian mid-shelf and oceanic islands. 83 records from Roter Berg Werdau (Leubnitz). 218 records from Land and freshwater molluscs of Northern Spain. 724565 records from Finnish Floristic Database (Literature Sources). 1 records from A new species of the hermit crab genus Alainopaguroides McLaughlin, 1997 (Crustacea: Decapoda: Anomura: Paguridae) from the South China Sea. 25 records from Base de données en ligne d'observations naturalistes de mammifères marins. GEPOG & LPO. 21 records from Caddisflies (Insecta: Trichoptera) from Santa Catarina Lachatao, Oaxaca, México: New species, new geographical records, and checklist. 6331 records from Base de datos de la flora de la Reserva de la Biosfera Chamela-Cuixmala, Jalisco, México. 99 records from Schwanner Warte / Kinderhaus St. Elisabeth Waldplatz. 98 records from Données opportunistes sur les odonates. 347 records from Orchideenstandort Nostengraben - Kretzberg (Oßmaritz). 5 records from Myrmeleon almohadarum sp. nov., from Spain and North Africa, with description of the larva (Neuroptera Myrmeleontidae). 14980 records from Données Entomologiques A. HORELLOU 1988-2018. 2 records from A new species of Paralithoxus (Siluriformes: Loricariidae: Ancistrini) from the highlands of Serra da Mocidade, Roraima State, Brazilian Amazon. 285 records from Données du/de la naturaliste Cousin Richard provenant de la base de donnée du SINP Île-de-France CETTIA. 7 records from Lizards in pinstripes: morphological and genomic evidence for two new species of scincid lizards within Ctenotus piankai Storr and C. duricola Storr (Reptilia: Scincidae) in the Australian arid zone. 632 records from 2019_NSMK_PL. 48 records from ZUEC-ECH - Coleção de Echinoidea do Museu de Zoologia da UNICAMP. 1 records from Different continents, same species? Resolving the taxonomy of some Holarctic Ancylis Hübner (Lepidoptera: Tortricidae). 1696 records from Herbier National de Guinée (HNG). 8 records from Revision of Afrotropical Silky Lacewings (Neuroptera: Psychopsidae). 24 records from EDIT - ATBI in Gemer area (Slovakia). 22113 records from Global compendium of Aedes albopictus occurrence. 325 records from Inventaire malacologique de la RNR des Marais de Stors. 148 records from Colección de Herpetología de la Universidad del Quindío (HERPETOS-UQ). 88 records from Teich Berlin Wuhlheide. 69 records from On a collection of hydroids (Cnidaria, Hydrozoa) from the southwest coast of Florida, USA. 5 records from A new Epeorus (Caucasiron) (Ephemeroptera: Heptageniidae) species from Turkey based on molecular and morphological evidence. 150 records from AKG-Gelände (Bensheim). 1 records from Occurrence of mammalia relicts at site Raagelund. 3740 records from Respaldo de las colecciones de tejidos del Museo de Zoología, Departamento de Biología Evolutiva, Facultad de Ciencias, UNAM. 3 records from A new species of velvet skate, Notoraja sereti n. sp. (Rajiformes: Arhynchobatidae) from Papua New Guinea. 203 records from Insectos de la expedición al municipio de San Francisco, Cundinamarca - Caracterizaciones Humboldt. 348 records from Naturschutzgebiet Heiliger Hain (Wahrenholz). 1121 records from Walter Herwig 1978 (FFS): SeaStars (Echinodermata, Asteroidea). 188 records from Atomariine Beetle (Coleoptera) records for Britain and Ireland to 1992. 2714 records from Données de la Réserve Naturelle Nationale de Saint-Quentin-en-Yvelines provenant de la base de donnée du SINP Île-de-France CETTIA. 17908 records from Colección de Peces del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P). 35 records from New species of Ochodaeus Dejean from Madagascar II (Coleoptera: Scarabaeoidea: Ochodaeidae). 94 records from Caddisflies (Insecta: Trichoptera) from Maranhão State, Northeast Region, Brazil: A new species, checklist, and new geographical records. 866 records from HUEMG herbarium - Universidade do Estado de Minas Gerais - Campus Carangola - Herbário Virtual REFLORA. 31 records from Revision of the Genus Leptogomphus Selys in Borneo, including gene trees and a two marker molecular phylogeny (Odonata: Anisoptera: Gomphidae). 209 records from Lebensraum Gesamtschule (Langerwehe). 243 records from Antarctic Amphipoda. 5 records from Two new species of the genus Microlysias (Crustacea, Amphipoda, Tryphosidae) from Korean Waters. 1654 records from RAVON (NL) - Fish observations extracted from Redeke (1907). 2497 records from Données des collections d'algues du MNHN. 2253 records from SP-Algae - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo - Coleção de Algas. 905 records from Coléoptères Silphidés du département du Loiret. 76 records from A synopsis of Phyllogomphoides Belle, 1970 (Odonata: Gomphidae) of Mexico: taxonomy and distribution. 3272 records from Mammifères marins Guadeloupe Antilles françaises (AET). Suppléments. 118 records from Observation des insectes sur le territoire de la Métropole Rouen Normandie. 3 records from New erythroneurine leafhopper species from the Australian realm (Hemiptera: Cicadellidae: Typhlocybinae). 31150 records from Effects of Fecal Input, Environmental Conditions, and Environmental Sources on Enterococci Concentrations in an Estuarine Ecosystem. 192 records from Alterra (NL) - Microarthropods inventory in Cranendonck area. 136 records from Tejidos colectados en la caracterización biótica para la conservación de especies amenazadas en el área de influencia del Oleoducto Bicentenario, departamentos de Arauca y Casanare, Colombia. 2380 records from RMT Trawl catch from the 1984/85 V5 SIBEX2 voyage. 16 records from Hazel Dormouse in Ireland. 30 records from New taxa of Tateidae (Caenogastropoda, Truncatelloidea) from springs associated with the Great Artesian Basin and Einasleigh Uplands, Queensland, with the description of two related taxa from eastern coastal drainages. 1027 records from Programme ACT : Répartition Merle noir 1996 - 2000 Coordonnées GPS Lambert 93. 642 records from Colección Aracnológica del IADIZA-CCT CONICET Mendoza: IADIZA-CAI. 46 records from An der Ohm, (Wettsaasen). 185 records from Inventaire des odonates d'intérêt communautaire. 121 records from Restauración de flora y repoblamiento de fauna nativa en 1,000 hectáreas para el restablecimiento del corredor biológico costero en la Laguna Madre, Tamaulipas. 1893 records from Données de la collection de Hubert Piguet - Famille des Elateridae. 7479 records from BioGIS - Vascular plants - Israeli Gene Bank. 10 records from Taxonomic revision of Intybia Pascoe, 1886 species (Coleoptera, Malachiidae) of Thailand and Philippines. 13527 records from Distribution Atlas of Butterflies in Ireland 1979 (An Foras Forbartha). 1 records from A New Species of Deep-channel Electric Knifefish Compsaraia (Apteronotidae, Gymnotiformes) from the Amazon River. 259 records from Programme ACT : Répartition Alouette lulu 2009 - 2013 Coordonnées GPS Lambert 93. 1 records from An extraordinary new genus and species of Pseudachorutinae (Collembola: Neanuridae) from Colombia. 31115 records from 16S rDNA amplicon of Bacteria and Archaea Metagenome. 5 records from A new species of cave dwelling Neocarus (Acari: Opilioacaridae) from Bahia state, Brazil, with remarks on taxonomic characters. 3 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Squamata (no Serpentes) (MFA-ZV-Sq). 1 records from Acantorna-a new genus of Hymedesmiidae (Porifera, Demospongiae Poecilosclerida) from the western Aleutian Islands of Alaska with description of Acantorna tahoma n. sp.. 10611 records from NEOTROPICMYXO. A database of Myxomycetes from the Neotropics. 2 records from A new species of rheophilic cyprinid fish (Teleostei: Cyprinidae) from the Brahmaputra Basin, northeast India. 2 records from A new genus and species of owlfly from eastern and southern Africa (Neuroptera: Ascalaphidae). 16838 records from Akita Prefectural Museum, Observation Records of Birds in Akita Prefecture. 8114 records from South Dakota State University, The Severin-McDaniel Insect Research Collection. 2 records from Hieracium attenboroughianum (Asteraceae), a new species of hawkweed. 3 records from A new remarkable and Critically Endangered species of Astyanax Baird & Girard (Characiformes: Characidae) from Chapada Diamantina, Bahia, Brazil, with a discussion on durophagy in the Characiformes. 7887 records from Inventario florístico de la región Calakmul-parte baja de la región Lacandona (Cuenca alta del Usumacinta y Marqués de Comillas). 1 records from A new species of Limnonectes (Amphibia: Anura: Dicroglossidae) from Vietnam. 1963 records from Marine Turtles. 145 records from An Online Database of the Immatures of Coleoptera (Arthopoda, Insecta) Described from Brazil. 5 records from A new species of Sarmydus Pascoe, 1867 (Cerambycidae: Prioninae: Anacolini) from Nicobar Island, India. 1 records from First record of the genus Chandleriella Hlaváč (Coleoptera: Staphylinidae: Pselaphinae) from China, with description of a second species. 783 records from Programme ACT : Répartition Tourterelle des bois 2011 - 2015 Coordonnées GPS Lambert 93. 6 records from Revision of the genus Shairella Chûjô, 1962 (Coleoptera: Chrysomelidae: Galerucinae) from Taiwan, with descriptions of five new species. 1298 records from Vermont Orthoptera Records from Historic Dot Maps. 1 records from First description of the male of the eyeless spider Draconarius tortus Chen, Zhu & Kim 2008 from China (Araneae: Agelenidae: Coelotinae). 3933 records from Inventario y catálogo de ostrácodos recientes de los mares mexicanos. 6 records from Revision of the Australian Wet Tropics endemic rainbowfish genus Cairnsichthys (Atheriniformes: Melanotaeniidae), with description of a new species. 1 records from Dorcus tianlongi, a new species from central China (Coleoptera: Lucanidae: Lucaninae). 6488 records from Colección de Geraniales hasta Lamiales del Museo Botánico CORD - IMBIV. 416 records from Surveys of the East Coast Akalat, Sheppardia gunningi, in Arabuko-Sokoke Forest, 2005-2011. 2 records from Dolichogenidea fernandeztrianai sp. nov. (Hymenoptera: Braconidae, Microgastrinae) from Iran. 4 records from Nomenclatural changes in Mymaridae (Hymenoptera: Chalcidoidea). 169 records from Re-examination of the reef corals of Cocos (Keeling) Atoll, Charlie Veron. 2 records from A new species of Acanthella Schmidt, 1862 (Porifera, Demospongiae, Dictyonellidae) from northeast region, Brazil. 99 records from Naturgrundstück (Eutin). 4275 records from Stratigraphic distribution of marine palynomorph species recorded for the Miocene of ODP Hole 105-645E (Table 1). 21 records from New data on brachypterous Paederus (Coleoptera, Staphylinidae) of mainland China. 229 records from données araneologiques de LEENKNEGT Virginie. 5 records from Herbario virtual bosques secos de Colombia - Sección herbario ICESI. 20 records from A new sand frog from Namaqualand, South Africa (Pyxicephalidae: Tomopterna). 46 records from Revision of the genus Nephelomilta Hampson, 1900, with descriptions of twelve new species and two new subspecies (Lepidoptera, Erebidae, Arctiinae). 68910 records from Données de l'Observatoire de la Faune de Bourgogne. 255 records from Programme ACT : Répartition Perdrix rouge 2009 - 2013 Coordonnées GPS Lambert 93. 1000 records from Colección Herpetológica (Reptiles) del Museo de Historia Natural de la Universidad Industrial de Santander. 114 records from Host associations of Melanterius Erichson (Coleoptera: Curculionidae: Cleogonini), with a diagnosis and delimitation of the genus and description of five new species. 5 records from Taxonomic review of the genus Paranisitra Chopard (Orthoptera: Gryllidae: Eneopterinae: Nisitrini) with description of a new species from Mindanao. 677 records from Contribución al conocimiento taxonómico de los peces que habitan los sistemas acuáticos de la reserva de Calakmul, Campeche. 100 records from Demosponges from the sublittoral and shallow-circalittoral (<24 m depth) Antarctic Peninsula with a description of four new species and notes on in situ identification characteristics. 1207 records from Microbial diversity studies of Arabian Sea sediment. 6466 records from Anillamiento de Aves Sierra Nevada de Santa Marta - Proyecto Cruzando el Caribe. 107 records from Museu de Ciències Naturals de Barcelona: MCNB-Tissue. 14 records from Echinoderms from the Seaflower Biosphere Reserve. 198 records from Programme ACT : Répartition Alouette lulu 1996 - 2000 Coordonnées GPS Lambert 93. 24 records from Colección de diatomeas del Herbario "Jaime Andrés Rodríguez". LEB-Diatomea. 14275 records from Actualización de la base de datos de hongos macroscópicos de Jalisco. 1124 records from Odonata Specimens of Yamaguchi prefectural Yamaguchi Museum. 14 records from MVZ Herp Observations (Arctos). 245 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 78 records from Données de la naturaliste Anna Even. 1914 records from Herbario de Hongos de la Universidad de Salamanca: SALA-Fungi. 816 records from Espèces végetales sur sable roux du fourré de Ranobe, PK 32 Toliara. 154 records from Données de la structure Philofauna provenant de la base de donnée du SINP Île-de-France CETTIA. 7 records from A new species of the genus Bothriomyrmex Emery, 1869 (Hymenoptera: Formicidae: Dolichoderinae) from Costa Rica.. 61 records from pangolin and pangolin products seized by the customs and pangolin public aided record from 2010 to 2019. 60 records from The Australian Ciidae (Coleoptera: Tenebrionoidea): supplement. 100 records from (Table 5) Abundance distribution of the 'clavate' subspecies of the genus Globigerinelloides and Pseudoschackoina saundersi in the Lesches en Diois section. 81 records from Kystfuruskoger i Tysnes og Fusa. 2112 records from Stratigraphic distribution of marine palynomorph species recorded for the Miocene and lowermost Pliocene of ODP Hole 105-646B (Table 1). 29 records from Nomenclatural changes in the higher classification of the family Tettigometridae (Hemiptera: Fulgoroidea) with description of a new tribe and new species and a review of the Iranian tettigometrid fauna. 362 records from Centre d'Estudis Avançats de Blanes, Macroinvertebrados Limno. 1158 records from Modelación de la distribución geográfica de las Orchidaceae del Soconusco. 8 records from Die Bachspezies 2008/2009. 73 records from Big and beautiful: the Megaxyela species (Hymenoptera, Xyelidae) of East Asia and North America. 33 records from Waldstück am Schullandheim Bad Bederkesa. 31 records from Review of Anasillomos Londt, 1983 with the description of a new species (Insecta : Diptera : Asilidae). 4 records from New records of Iranian bark beetles (Coleoptera: Curculionidae, Scolytinae) and their host plants. 2898 records from DBL_Life. 205 records from Aves de la expedición en el páramo de Bijagual, Boyacá - Proyecto Boyacá BIO. 3350 records from Reef Check in Taiwan 台灣珊瑚礁體檢. 1 records from Données naturalistes d'Olivier DELZONS. 25 records from Thirteen new species of the spider genus Pholcus Walckenaer, 1805 (Araneae: Pholcidae) from China. 218 records from (Table 2) Abundance of planktonic foraminifera in ODP Hole 113-689B, small size fraction. 408 records from Colección Ornitológica de la Universidad Tecnológica del Chocó. 94 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-11. 195 records from Pedestrian mammals census in W National Park. 1178 records from Océanopolis mammifères marins en Bretagne 1993-2015. 1 records from A new species of Aphonopelma (Araneae: Mygalomorphae: Theraphosidae) from the Madrean pine-oak woodlands of northeastern Sonora, Mexico. 9 records from BLS Rare and Threatened Lichen Records: England. 1 records from New morphological information on Simulium wygodzinskyorum Coscarón & Py-Daniel, 1989 (Diptera: Simuliidae). 162 records from Schulhof Gymnasium Hürth Bonnstrasse. 145 records from Gronau - auf der Suche nach dem Neunauge. 95 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México. 1120 records from Programme national de science participative sur la Biodiversité Littorale (BioLit). 10 records from Epinephelus fuscomarginatus (Perciformes: Epinephelidae), a new species of grouper from off the Great Barrier Reef, Australia. 174 records from BIRDRACE Bon(n)apartemöwen. 1 records from Discovery of the transantarctic distribution of the genus Metanteon Olmi (Hymenoptera: Dryinidae), with description of a new species from New Caledonia. 538 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales del municipio de Pie de Pepe, Chocó. 3 records from A new species of the hermit crab genus Diogenes Dana, 1851 (Decapoda: Anomura: Diogenidae) from southern India. 1 records from The subfamily Cratocentrinae (Hymenoptera: Chalcididae): reappraisal of their morphological characters and review of the West Palaearctic species, with the description of two new species. 1540 records from NatureMap Calcrete Survey. 4183 records from Marine Bird Sighting Data, Arctic Marine Biodiversity Observing Network (AMBON) Chukchi Sea research cruise on the vessel Norseman II from 2015-08-09 to 2015-09-03. 101 records from Lynx 2002 présence Occasionnelle Mailles 10km Réseau Loup-Lynx ONCFS. 1 records from A new species of Homo from the Late Pleistocene of the Philippines. 1 records from Systematic revision of the Andean butterfly genus Orophila Staudinger, 1886 (Lepidoptera: Nymphalidae: Biblidinae). 69 records from Entdeckertour am Muldestausee 1/05. 1 records from Deux nouvelles espèces d’ Aloe L. (Xanthorrhoeaceae, Asphodelaceae), section Lomatophyllum Rowley, de Madagascar. 104 records from BID-Malawi-Arctiidae-Biodiversity-Data. 1 records from Spiders of the mungaich group from Western Australia (Araneae: Salticidae: Euophryinae: Maratus), with one new species from Cape Arid. 2534 records from Elaboration de table de tarif de cubage multispécifique (I). 2 records from pp 56 - 66, plates 1 - 4 in Monographie des Libellulidées d'Europe. 2007 records from Demersal and pelagic species of fish and squid from the Patagonian shelf. 5 records from Two new Cyphoderus (Collembola: Paronellidae) of “ tridenticulati ” and “ bidenticulati ” groups from Brazilian Amazon. 461 records from Occurrences of Boeckella at high latitudes in the southern hemisphere. 2 records from A new species of Rock Gecko genus Cnemaspis (Squamata: Gekkonidae) from Western Sarawak, Malaysia. 22 records from Wildgehege Glauer Tal (Naturpark Nuthe-Nieplitz). 122 records from BIOTOPE_2017_12_18. 2 records from Description of a new diminutive, rupicolous species of day-gecko (Squamata: Gekkonidae: Cnemaspis) from southern Sri Lanka. 38 records from Taxonomic revision of the Cis-Andean species of Mylossoma Eigenmann & Kennedy, 1903 (Teleostei: Characiformes: Serrasalmidae). 108 records from BIRDRACE Diesmal sehen wir mehr. 16 records from Insect Collections of Okomu National Park- Nigeria. 50874 records from University of Minnesota Insect Collection. 4 records from Sangpradubina, an astonishing new mayfly genus from Thailand (Ephemeroptera: Leptophlebiidae: Atalophlebiinae). 47 records from ARABEL - Arachnologia Belgica. 765 records from Mammal records from Britain from the Atlas of Mammals (1993), with some subsequent records. 393 records from Heinersdorfer Sumpfwiese. 1346 records from Weevils of Poland. 1 records from A new species of Caligus Müller, 1785 (Copepoda: Siphonostomatoida: Caligidae) from coral reef plankton in the Mexican Caribbean. 8 records from The genus Asiagomphus in Vietnam, with descriptions of three new species, and first descriptions of the male of Asiagomphus auricolor (Fraser, 1926) and of the female of Asiagomphus reinhardti Kosterin & Yokoi, 2016 (Odonata: Gomphidae). 8 records from Generic assignment of Leuciscus kurui Bogutskaya from the upper Tigris drainage, and a replacement name for Alburnus kurui Mangit & Yerli (Teleostei: Leuciscidae). 26 records from New records of eumenine wasps (Hymenoptera: Vespidae: Eumeninae) from Russia with description of a new species of Leptochilus de Saussure, 1853. 4 records from A new genus and species of Stigmoderini Lacordaire, 1857 (Coleoptera: Buprestidae: Buprestinae) from Southeast Brazil with notes on its hypothesized mimicry complex. 1761 records from Arachnida of Costa Rica (INBio). 22680 records from Arctic Species Trend Index (ASTI) : Marine. 2 records from Revision of the Melanogaster jaroslavensis group (Diptera: Syrphidae), with description of a new species from Afghanistan. 675 records from Données du naturaliste RADOGEWSKI Alain provenant de la base de donnée du SINP Île-de-France CETTIA. 188 records from Occurrence of some antimalarial plants from Cameroon. 14257 records from Inventaire de la flore du PNRLG 2016 (Gironde). 174 records from Antarctic pycnogonids. 24 records from New gnathiid isopod crustaceans (Cymothoida) from Heron Island and Wistari Reef, southern Great Barrier Reef. 63 records from Inventaire des espèces végétales de la vallée de Gounti Yéna (Niamey). 45556 records from MLZ Bird Collection (Arctos). 74 records from Birdrace_Gätkes_Schergen-Helgoland. 12 records from Leiocassis rudicula (Teleostei: Siluriformes: Bagridae), a new catfish from eastern Borneo. 5 records from Two new damselflies of the genus Idiocnemis Selys from Gulf Province, Papua New Guinea (Odonata: Platycnemididae). 14 records from The megadiverse fauna of Neotropical Cerambycidae (Coleoptera): Notes, descriptions, new records, new species, and revalidations. 125 records from Naturschutzgebiet Müchelholz (Mücheln). 163 records from Wiese am Waldrand (Gurtweil). 5 records from New records and updated distribution of the ant-like jumping spider genus Zuniga Peckham & Peckham, 1892 (Salticidae: Salticinae: Sarindini) in the Neotropics. 2 records from A new species of Phintella from Angola (Araneae: Salticidae). 2 records from Tardigrada and Rotifera from moss microhabitats on a disappearing Ugandan glacier, with the description of a new species of water bear. 25 records from New records of Munidopsis (Crustacea: Anomura: Galatheidae) from New Zealand with description of two new species from a seamount and underwater canyon. 11 records from The genus Diphasia L. Agassiz, 1862 (Cnidaria, Hydrozoa) in Northwest Africa. 11840 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2018. 37 records from uncultured bacterium Targeted Locus (Loci). 381519 records from DNV GL Statfjord. 1 records from A new species of Odontozona Holthuis, 1946 (Crustacea: Decapoda: Stenopodidea: Stenopodidae) from the Caribbean Sea. 4 records from Coralliidae (Anthozoa: Octocorallia) from the INDEMARES 2010 expedition to north and northwest Spain (northeast Atlantic), with delimitation of a new species using both morphological and molecular approaches. 118 records from Birdrace-Birding_Bentheim-Grafschaft_Bentheim. 3 records from (Table 2) Mercury concentration in hair of Northwest Greenland polar bears (Ursus maritimus). 7 records from Données naturalistes d'Olivier VILLEPOUX. 1822 records from Galathea II, Danish Deep Sea Expedition 1950-52. 143 records from UWYMV Herpetology Collection (Arctos). 279 records from Atlas des Hyménoptères Pompilidae du Massif armoricain et des départements voisins : prospections 2018. 163 records from Endofauna abundance in 2006-10 from an experiment in the Wadden Sea of List, Sylt. 11837 records from NCSM Non-molluscan Invertebrates Collection. 86 records from Antarctic Parborlasia corrugatus. 106407 records from The AAU Herbarium Database. 14069 records from Midden-Limburg Fish Ponds Survey. 5 records from Description of lithologic section units of IODP Hole 325-M0046A. 7 records from Thylacosceles Meyrick new to China, with descriptions of four new species (Lepidoptera: Stathmopodidae). 53025 records from Herbarium Senckenbergianum (FR) - Fungi. 6478 records from National System of Protected Areas in Poland - Animals. 1994 records from Fish Collection of Coastal Branch of Natural History Museum and Institute, Chiba. 1 records from Three new species of the family Phytoseiidae (Acari: Mesostigmata) from Turkey. 5 records from Review of the Eulimnadia (Branchiopoda: Spinicaudata: Limnadiidae) from Argentina with the description of a new species. 2 records from Contribution to the knowledge of the Clytrini of the Eastern Mediterranean, the Near East and the Arabian Peninsula, with descriptions of four new species (Coleoptera: Chrysomelidae: Cryptocephalinae). 828 records from Sistematización de la Colección Entomológica Forestal del CENID-COMEF. 411 records from Sixty new dragonfly and damselfly species from Africa (Odonata). 895 records from Geometridae de France métropolitaine. 4167 records from Colecção Entomológica do Museu de História Natural de Maputo. 238 records from Vegetación asociada a la ciénaga de Bete, municipio del Medio Atrato, Chocó 2008. 2829 records from (Figure 3) Stratigraphic distribution of planktonic foraminifera in the Neogene of ODP Hole 122-761B. 18 records from Revision of the Palaearctic Trachusa interrupta species complex (Apoidea: Anthidiini) with description of four new species. 991 records from SPC CoFish Invertebrates Observations Marshall Islands 2007. 25 records from Leiolima iberica, a new harvestman genus and species from the Iberian Peninsula (Arachnida, Opiliones, Sclerosomatidae). 724 records from Heritage Trees of Ireland. 16618 records from Suivi Temporel des Libellules (STELI). 1 records from Herpetological (amphibian & reptile) specimens of Ryukyu University Museum (Fujukan). 3 records from Three new species of Elachistidae (Lepidoptera: Gelechioidea) from India. 30854 records from First Bird Atlas. 2 records from Revision of the Oriental subgenus Patrisaspilota Fischer, 1995 (Hymenoptera: Braconidae: Alysiinae: Orthostigma Ratzeburg, 1844) with description of a new species from Papua New Guinea. 2 records from An annotated catalogue of the pygmy grasshoppers of the genus Criotettix Bolívar 1887 (Orthoptera: Tetrigidae) with two new Criotettix species from China. 1 records from Revision of Family Megacalanidae (Copepoda: Calanoida). 2 records from Definition of the Lonchaea polyhamata species-group (Diptera, Lonchaeidae) with a description of new species. 10354 records from Inventaire de la flore de Charente-Maritime 2018. 2 records from A new species of Pelthydrus (s. str.) Orchymont, 1919 from Yunnan, China (Coleoptera: Hydrophilidae: Hydrophilinae: Laccobiini). 5 records from Description and molecular phylogeny of Axinella nayaritensis n. sp. (Porifera: Axinellida) from East Pacific and remarks about the polyphyly of the genus Axinella. 38 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 147 (N.S) n° 40 (2), 2012 - Données faune. 2 records from First record of the leafhopper genus Xenovarta Viraktamath (Hemiptera, Cicadellidae, Deltocephalinae) from India with description of a new species. 2808 records from Natura 2000 Vallée de la Seille. 10894 records from Occurrences of the invasive plant species Heracleum sosnowskyi Manden. in the Komi Republic territory (European North-East Russia). 100 records from Données d'observation d'écrevisses exotiques envahissantes en Haut de France et Normandie sur la période 2014 à 2018. 46 records from Freshwater fish records via iRecord - additional species. 1 records from A new species of Isthmura (Caudata: Plethodontidae) from the montane cloud forest of central Veracruz, Mexico. 9858 records from Inventario de Hymenóptera; parasítica en México. 19054 records from IMPACT OF SAHARAN DUST DEPOSITION ON BACTERIOPLANKTON IN MARINE SURFACE WATER. 1 records from Description of a new whiteflyı Pealius satakshiae Dubey (Hemiptera: Aleyrodidae) ı infesting Quercus leucotrichophora (Fagaceae) in the Western Himalayaı India. 3 records from Three new species of Tridentella Richardson, 1905 (Isopoda: Cymothoida: Tridentellidae) from New Caledonia. 989 records from Programme ACT : Répartition Pigeon ramier 2006 - 2010 Coordonnées GPS Lambert 93. 8499 records from Colección de insectos agrícolas del proyecto diversidad en sistemas de cultivos. 2 records from A new species of the genus Oxyporus Fabricius (Coleoptera: Staphylinidae: Oxyporinae) in Yunnan Province, China. 1785 records from 3Soil16S. 1 records from SJRP-Fungi - Herbário de fungos de São José do Rio Preto. 1 records from Synonymies, a new combination, and four new species in Amphicnaeia Bates (Coleoptera: Cerambycidae: Lamiinae). 715 records from Museu Valencià d′Història Natural - Fundación Entomológica Torres Sala: FETS. 1400 records from Aves de la expedición en lago de Tota, Boyacá - Proyecto Boyacá BIO. 4166 records from Gunma Museum of Natural History, Fungi Specimen. 2 records from HZI (GBF) Reichenbach Collection of Myxobacteria. 1573 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Bryozoa. 76 records from BIRDRACE Nachtigallen. 33182 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Arachnology National Collection (MACNAr). 1284 records from ConDidact Citizen Science Surveys - Amphibians 2007. 61 records from Données de Midi-Pyrénées transmises par Pascal Peyrache.. 252 records from (Table 3) Distribution of late Cretaceous nannofossils in DSDP Hole 77-538A. 2 records from Kirchenforst. 5 records from Three new species of Leptanilloides Mann from Andean Ecuador (Formicidae: Leptanilloidinae).. 12558 records from Bacterial diversity in snow from mid-latitude mountain areas: Alps, Eastern Anatolia, Karakoram and Himalaya.. 13 records from Données naturalistes de THÉVENOT Jessica. 4 records from Two new genera and five new species of Tullbergiidae (Collembola) from the southern Appalachian Mountains of North America, with redescription of Tullbergia clavata Mills. 180 records from (Table 6) Abundance distribution of the 'clavate' subspecies of the genus Globigerinelloides in DSDP Hole 79-545. 50 records from Occurrence of mammalia relicts at site Biedermann. 55 records from Biodiversidad del orden Araneae (Arachnida) de las Islas del Golfo de California, México. 35084 records from Inventaire de la flore de Lot-et-Garonne 2017. 9530 records from Oiseaux nicheurs de France métropolitaine 1970-1975 - nidification possible. 1 records from The oldest representative of the modern snipe fly genus Symphoromyia (Diptera: Rhagionidae). 23136 records from PAH-contaminated sediment from the Lagos Lagoon, Nigeria. 31 records from Salud coralina de las comunidades arrecifales de la Isla Cayo Serranilla durante la Expedición Seaflower 2017 - Proyecto Colombia BIO. 676 records from Lucanidae. 690 records from Field Study Group of the Dutch Mammal Society (NL) - 2012 - Mammal Survey Galicia, Spain. 1 records from A new brachypterous Filchneria and two new generic records for China, Arcynopteryx and Pictetiella (Plecoptera: Perlodidae). 27670 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 44 records from Distribución de la Nutria (Lontra longicaudis) en la cuenca baja del río Sinú en el departamento de Córdoba. 3 records from Description of a new species of the genus Cnemaspis Strauch, 1887 (Reptilia: Squamata: Gekkonidae) from the Nilgala Savannah forest, Uva Province of Sri Lanka. 276 records from Birds Specimens of Akita Prefectural Museum. 2 records from A new micropterous species of Leuctra (Plecoptera: Leuctridae) from the Lesser Caucasus (Georgia). 1 records from A new species in the troglomorphic scorpion genus Troglotayosicus from Colombia, representing the northernmost known record for the genus (Scorpiones, Troglotayosicidae). 2 records from A new species of Phlogophora Treitschke (Lepidoptera: Noctuidae) from China. 100 records from Données naturalistes de LE GLOANEC Vincent. 75 records from Species diversity of Myrmecofauna (Hymenoptera, Formicidae) on the southern slope of Djurdjura National Park (Northern Algeria). 5 records from The oribatid mite genus Topalia in Australia (Oribatida: Nosybeidae) and the taxonomic status of related families and genera. 25 records from MSUM Ichthyology and Herpetology Collections. 2 records from Three new species of Entomobryoidea (Collembola: Entomobryomorpha) from Brazilian Caatinga-Cerrado transition, with identification keys to Brazilian Cyphoderus, Pseudosinella and Trogolaphysa species. 1658 records from ZUEC-HEM - Coleção de Hemiptera do Museu de Zoologia da UNICAMP. 13 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Tecidos (ZUFMS-TEC). 5260 records from Whale catches in the Southern Ocean. 133065 records from UWFC Ichthyology Collection. 41 records from Lynx 1999 présence Régulière Mailles 10km Réseau Loup-Lynx ONCFS. 813 records from Programme ACT : Répartition Tourterelle des bois 1996 - 2000 Coordonnées GPS Lambert 93. 6811 records from Auburn University Museum of Natural History Invertebrates. 1 records from On the genus Paleonura (Collembola: Neanuridae: Neanurinae) from the Americas and description of a new species from Puerto Rico. 1 records from Morphological and molecular distinction of two Fridericia species (Clitellata, Enchytraeidae) having same spermatheca type. 27 records from Monophyly, review, six new species and DNA barcode of micropterous Afromontane Afropictinus (Heteroptera: Aradidae). 58 records from Mamíferos laguna El Tinije. 3575 records from DREAL_PACA_-_N2000_-_Parc_Naturel_Régional_du_Queyras_2017_12_18. 24 records from Eurobodalla Regional Botanic Gardens. 63099 records from CABI Africa Invasive and Alien Species data. 31014 records from River Biologists' Database (EPA). 26 records from Rhamphomyia Meigen of the Canadian Arctic Archipelago, Greenland and Iceland (Diptera: Empididae). 4 records from Seven species of Pseudopecoeloides Yamaguti, 1940 (Digenea, Opecoelidae) from temperate marine fishes of Australia, including five new species. 70628 records from Tiroler Landesmuseum Ferdinandeum. 75 records from The bees of the genus Colletes Latreille (Hymenoptera: Colletidae) of the Caucasus region. 91 records from Anfibios y reptiles de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 17824 records from MPUC - Herbário do Museu da Pontifícia Universidade Católica do Rio Grande do Sul. 13868 records from Données faune Nature 18 - 2017. 104 records from BIRDRACE Die Vriesischen Feigen-Vögel (VFV). 855 records from Données supplémentaires Atlas des Mammifères marins. 53 records from Données du/de la naturaliste Dubois Yves provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from Bryozoans Specimens of Akita Prefectural Museum. 9 records from Leptobasis linda sp. nov. from Ecuador (Odonata: Coenagrionidae). 18 records from Anfibios presentes en el Cerro Jánano. 120 records from Données espèces - Expertise IPE 79. 16 records from Eight new species of the spider genus Khorata Huber, 2005 (Araneae: Pholcidae) from China. 179 records from Área Otún Quimbaya - Densidad poblacional valores objeto de conservación Santuario de Fauna y Flora Otún Quimbaya, 2016. 105 records from Lynx 2015 présence Occasionnelle Mailles_10km_LAEA Réseau Loup-Lynx ONCFS. 609 records from SPC PROCFish/C Invertebrates Observations Kiribati 2004. 305 records from Rohrmeistereiplateau und angrenzendes Gebiet. 4913 records from CUMV Fish Collection. 9 records from Survey and monitoring records for Scottish Wildlife Trust reserves from reserve convenors and Trust volunteers - Unassessed data. 7 records from New Oligaphorura species (Collembola: Onychiuridae) from the forests of East Asia. 1 records from New record for the deep-sea genus Tripoplax (Mollusca: Polyplacophora) in the eastern Pacific. 909 records from South American Antarctic Marine Biodiversity Literature. 189 records from Chas.H. O'Donoghue, D.Sc. & Dora de Watteville,M.A. The fishery grounds near Alexandria. XX-Bryozoa. Notes and Memoirs No 34. Hydrobiology and Fisheries Directorate, Egypt.. 81 records from Métropole_Nice_Côte_d'Azur_2017_12_18. 308 records from Naturmiljø Bergensbanen 2015 (project number 616033). 1930 records from Données de la naturaliste Lemoine Delphine provenant de la base de donnée du SINP Île-de-France CETTIA. 615 records from Modelación de la distribución y abundancia de las subespecies de venado cola blanca en México: implicaciones de conservación y manejo. 4 records from First record of the genus Ptilocerus in the Australian Region, with the description of two new species (Hemiptera: Heteroptera: Reduviidae). 141 records from Collection Hydrozoa - ZSM München. 1 records from Description of the male of Phoebe ornator (Tippmann, 1960) (Coleoptera: Cerambycidae: Lamiinae: Hemilophini), analysis of the species biogeography, and first observation of chromatic gender dimorphism in Hemilophini. 35 records from Inventaire et suivi de la faune écrasée. 596 records from Lower Albian l'Arboudeysse section (Niveau Paquier) individuals per gram sediment of benthic foraminifera, in SE France. 1 records from New Species Of The Genus Oronoqua Fennah (Hemiptera: Auchenorrhyncha: Fulgoroidea: Issidae) From Inland Ecuador. 45139 records from Système d’Information Régional sur la Faune et la Flore - FNE Centre-Val de Loire - Données 2016. 1000 records from nsmk_mm_2019. 47 records from Squalius namak, a new chub from Lake Namak basin in Iran (Teleostei: Cyprinidae). 1 records from Morphological and molecular analyses confirm the occurrence of two sympatric Lysmata shrimp (Crustacea, Decapoda) in the southwestern Atlantic. 68 records from Streuobstwiese. 10 records from Description of a new species of Caridina (Crustacea: Decapoda: Atyidae) from two Micronesian islands (Guam and Babeldaob). 45378 records from Western Australian Museum provider for OZCAM. 176 records from Rund um den Eichwald,Schulhof Friedrich Fröbel Gymnasium- Bad Blankenburg. 71 records from Phytoplankton abundance in the Wadden Sea off List, Sylt, North Sea in 2007. 197 records from ABC_Event data recorded on a day trip to Mongolwe and Chikala Hills Forest Reserve, Machinga District. 3983 records from Diversidad vegetal en un gradiente en la Sierra Madre Occidental: flora y vegetación de la Región de San Javier y Yécora, Sonora. 81 records from Rückkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach. 233 records from Flora vascular y no vascular: expedición Cuenca Media del río Chicamocha - Proyecto Boyacá BIO UPTC. 234 records from Migratory shorebirds (sandpipers and plovers) in Hokkaido. 148933 records from Bryophyte data for Great Britain from the British Bryological Society held by BRC: Atlas 2014. 3 records from Gyrinus rhyssonotum sp. n., a new species of Gyrinidae (Coleoptera: Adephaga) from northern Brazil. 1 records from Studies in Australian Tettigoniidae: New Fully-winged Agraeciini From Northeastern Australia (Orthoptera: Tettigoniidae; Conocephalinae; Agraeciini). 9 records from A New Species Of Novius Mulsant From New Caledonia (Coleoptera: Coccinellidae: Noviini). 1 records from Phasmatodea Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 1009 records from Programme ACT : Répartition Merle noir 2012 - 2016 Coordonnées GPS Lambert 93. 1 records from The discovery of Euryrhynchidae (Crustacea: Decapoda) in India, with the description of a new genus and species. 1 records from The nymph, habitat, and status of Eatonigenia in China (Ephemeroptera: Ephemeridae). 5 records from Cave-inhabiting Neobisiidae (Arachnida: Pseudoscorpiones) from China, with description of four new species of Bisetocreagris Ćurčić. 7 records from New taxa and new records of Deltocephalini leafhoppers from Thailand (Hemiptera: Cicadellidae: Deltocephalinae). 225 records from L’évaluation environnementale du projet du barrage de la retenue d'eau, de Guinea Alumina corporation à sangaredi, Boké (CESP2016-022). 4617 records from Inventaire de la flore du Grand Poitiers 2009. 1 records from A new Portholefish of the genus Diplophos (Stomiiformes: Gonostomatidae) from the western Pacific Ocean. 1031 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 143 (N.S) n° 36 (1), 2008 - Données faune. 253 records from Données naturalistes d'Olivier LAURENT. 1 records from A new species of the Scinax catharinae group (Anura: Hylidae) from southeastern Brazil. 22726 records from Restauración y conservación de Isla Guadalupe. 13 records from Coleção de Coleoptera da Universidade de Brasília. 5044 records from Mollusca specimens of Wakayama Prefectural Museum of Natural History. 96 records from Warnowtal (Rostock). 6 records from Wuhle - Brücke / B1. 6 records from A new western Atlantic snapping shrimp of the Alpheus macrocheles group (Caridea, Alpheidae) revealed by morphological, molecular and color data. 3055 records from Marie-Victorin Herbarium (MT) - Bryophytes. 26 records from New enigmatic species of the genus Pediobius (Hymenoptera, Eulophidae) from Afrotropics, with notes on related genera. 151 records from Código de barras de ejemplares de la Colección Nacional de Mamíferos del Instituto de Biología, UNAM. 2 records from Three Echiniscidae species (Tardigrada: Heterotardigrada) new to the Polish fauna, with the description of a new gonochoristic Bryodelphax Thulin, 1928. 2747 records from Compost microbe establishment and growth in agricultural soils. 202122 records from National Benthic Inventory. 88 records from Occurrence of mammalia relicts at site Laugerie-Haut e-Est. 111 records from BIRDRACE Die Wendehälse. 3 records from Review of genus Hydropsyche Pictet 1834 (Insecta: Trichoptera: Hydropsychidae) from India. 1303 records from Utah State University, Intermountain Herbarium. 1518 records from Herpetofauna de la región del Mar Muerto, Oaxaca-Chiapas. 42 records from "Natur macht Schule 2" Natur im Wohngebiet Gorndorf. 61924 records from CAS Entomology (ENT). 243726 records from Carnet B Lorraine. 1174 records from Naturalis Biodiversity Center (NL) - Pisces. 27 records from Halaelurus maculosus n. sp. and H. sellus n. sp., two new species of catshark (Carcharhiniformes: Scyliorhinidae) from the Indo-West Pacific.. 5 records from Eine neue Art der Gattung Quedius STEPHENS aus Syrien (Coleoptera, Staphylinidae, Staphylininae, Staphylinini, Quediina. 320 records from Myxomycetes collection of the University of Eastern Finland. 61762 records from Données du/de la naturaliste Bottinelli Julien provenant de la base de donnée du SINP Île-de-France CETTIA. 26813 records from Seasearch Marine Surveys in England. 20 records from New data on the fauna of China, part I: the taxonomy of the millipede family Julidae (Diplopoda). 53 records from The water mite genus Aspidiobates Lundblad, 1941 from Australia (Acari: Hydrachnidia: Hygrobatidae) with the description of two new species. 9 records from A review of the genus Coccoglypta Pilsbry, 1895 (Gastropoda: Pulmonata: Camaenidae). 307 records from Tejidos de la expedición en el páramo de Rabanal, Boyacá - Proyecto Boyacá BIO. 2963 records from Collection Trichoptera - SMF. 16 records from Seven new species of the Stenus cirrus group (Coleoptera, Staphylinidae) from Guangxi, South China. 160 records from Integrierte Gesamtschule Flensburg Wiemoosgraben. 132 records from The pholcid spiders of Sri Lanka (Araneae: Pholcidae). 255 records from Occurrence of mammalia relicts at site Raj Cave. 64 records from First record to Brazil of one genera and seven species of Psychodidae (Diptera) with further new records for 10 countries on the Neotropics. 878 records from Arizona State University Hasbrouck Insect Collection. 2536 records from Invasive Alien Species Occurrence in Ghana. 63364 records from CCAMLR historic KRILL. 1015 records from Inventario ictiofaunístico de los humedales de Puerto Morelos, Quintana Roo. 3375 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase. 124 records from Birdrace-Die_Ackermännchen-Schalm-Eder-Kreis. 35 records from The Xiphydria annulitibia group in northeastern Asia (Hymenoptera, Xiphydriidae). 1480 records from MGC Herbarium of University of Malaga (Spain): MGC-Algae dataset. 3379 records from Lista florística de la Costa Grande del estado de Guerrero. 13 records from Espèces envahissantes de la Guinée forestière extraites dans la base de données de CRRA Sérédou Macenta, IRAG.. 452 records from Helmintos parásitos de peces dulceacuícolas de cuencas hidrológicas del Centro-Norte de México (Durango). 155 records from Review of the Spirobolida on Madagascar, with descriptions of twelve new genera, including three genera of ' fire millipedes' (Diplopoda). 60 records from Amtsrain Apolda-Zottelstedt. 128 records from Inventaire des reptiles 2014. 589 records from Programme ACT : Répartition Pie bavarde 2005 - 2009 Coordonnées GPS Lambert 93. 46057 records from Diversidad y dinámica del fitoplancton marino en la bahía de Acapulco, Guerrero. 53 records from Calcareous sponges of the Western Indian Ocean and Red Sea. 230 records from (Table 2) Range chart for planktonic foraminifers from ODP Hole 111-677B. 1 records from West Palaearctic species of the genus Diostracus Loew, 1861 (Diptera: Dolichopodidae). 151 records from Occurrence of mammalia relicts at site Stadel im Hohlenstein. 20440 records from Inventaire de la flore de Charente-Maritime 2017. 160 records from Die Oribatiden-Arten (Acari) eines suedwestdeutschen Buchenwaldes I.. 55 records from Taxonomic studies on potter wasps (Hymenoptera: Vespidae: Eumeninae) of south India. 4853 records from Inventaire des espèces végétales du sous bois des plantations de Teck de la forêt naturelle de la Lama. 97 records from Dorfrand Mauderode. 1 records from Eucharitidae new to the fauna of Saudi Arabia (Hymenoptera: Chalcidoidea), with the description of a new species and the previously unknown male of Eucharis (Psilogastrellus) albipennis Bouček. 152 records from (Table 2) Abundance of Globigerinoides sacculifer and Globigerinoides ruber and oxygen and carbon stable isotopes of different planktonic foraminifers at DSDP Hole 78-543. 61 records from Shrews of Poland. 2 records from A molecular phylogenetic hypothesis for the Asian agamid lizard genus Phrynocephalus reveals discrete biogeographic clades implicated by plate tectonics. 17755 records from K-State Museum of Entomological and Prairie Arthropod Research. 4 records from New distributional records and life stage description of Caenis species (Ephemeroptera: Caenidae) from Brazil. 28711 records from TPWD HARC Texas Coastal Fisheries Corpus Christi Bay Bag Seine. 92 records from The genus Leptostylopsis of Hispaniola (Coleoptera, Cerambycidae, Acanthocinini). 186 records from New Staphylinidae (Coleoptera) records with new collection data from New Brunswick, Canada. I. Aleocharinae. 31 records from STELI 2015 Saint-Pée-sur-Nivelle (64) par l'association EcoGIS. 4035 records from Marine benthic dataset (version 1) commissioned by UKOOA. 172 records from Données du/de la naturaliste Roquinarc'h Océane provenant de la base de donnée du SINP Île-de-France CETTIA. 1278 records from Inventaire des Crustacés Décapodes de France métropolitaine. Données du compte CardObs 1113. 6775 records from Données du naturaliste MIGUET Pierre provenant de la base de donnée du SINP Île-de-France CETTIA. 946 records from Database on reference specimens for medicinal plants of the Fabaceae family, conserved at the CNARP herbarium. 12 records from A revision of the Chilean Brachyglutini - Part 4. Revision of Achilia Reitter, 1890: A. puncticeps and A. approximans species groups, with description of seven new species (Coleoptera: Staphylinidae: Pselaphinae). 67797 records from Microbial diversity in the Benguela coastal upwelling system as derived from 16S rRNA sequencing and RNA Stable Isotope Probing (SIP). 1 records from Description of the imago of Neocapritermes utiariti (Isoptera: Termitidae: Termitinae). 2068 records from Colecta botánica: área maya región de la Reserva Calakmul, Campeche. 661 records from Etude floristique de la forêt marécageuse de Lokoli au Bénin. 4 records from Description And Phylogeny Of Staminodeus, A New Genus Of Derelomini (Coleoptera: Curculionidae) Associated With Cyclanthaceae. 1024 records from BUND - Dassower See (Lübeck/Dassow). 59978 records from Données naturalistes de Monsieur François FOURNIER. 1000 records from Fungal specimens of Faculty of Agriculture and Life Science, Hirosaki University. 2 records from Five new species of Macrostomus Wiedemann and a checklist of Empididae (s. str.) (Diptera) from Bolivia. 54016 records from Naturhistorisches Museum Mainz, Feldbeobachtungsdaten Pflanzen. 1 records from Gymnoamblyopus novaeguineae, a new genus and species of worm goby from Papua New Guinea (Gobiidae: Amblyopinae).. 9 records from Jeu de données convention FEGVE-SPN (numéro 2). 4 records from Sächsische Schweiz (Wehlener Gebiet). 19 records from Schizorhynchia Meixner, 1928 (Platyhelminthes, Rhabdocoela) of the Iberian Peninsula, with a description of four new species from Portugal. 29 records from Ours 2004 présence Occasionnelle Mailles 10km LAEA Réseau Ours brun ONCFS. 28 records from Creación de un área protegida pública local en los municipios de Roldanillo, La Unión y Toro.. 570 records from Cuxhavener Küstenheiden. 669 records from Hatikka Observation Database. 1740 records from UWYMV Bird Collection (Arctos). 751 records from Données naturalistes de Monsieur JOURDE Rémi. 873 records from Programme ACT : Répartition Geai des chênes 2008 - 2012 Coordonnées GPS Lambert 93. 16 records from On the genus Tylorida Simon, 1894 with the first record of the genus Atelidea Simon, 1895 from India (Araneae: Tetragnathidae, Leucauginae). 42 records from Occurrence of mammalia relicts at site l´Abri de Campalou. 445925 records from PlutoF platform observations. 1 records from A new species of Allomallodon Santos-Silva and Galileo, 2010 from Bolivia (Coleoptera: Cerambycidae: Prioninae: Macrotomini). 6 records from Two new species of Corumbataia (Hypoptopomatinae: Loricariidae) from Rio Corrente, upper Rio Paraná basin, Brazil. 582 records from Occurrence data of Swallowtail butterflies (Lepidoptera: Papilionidae) in the Zoology Museum of Makerere University. 2 records from Four species of Tubifex Lamarck (Annelida: Oligochaeta: Naididae) from Tibet, China. 8 records from New data on species diversity of Annelida (Oligochaeta, Hirudinea) in the Kharbey lakes system, Bolshezemelskaya tundra (Russia). 84 records from (Appendix B) Calcareous benthic foraminifers in ODP Hole 123-765C. 5 records from The genus Spirontocaris Spence Bate, 1888 (Caridea, Decapoda, Thoridae) in western Mexico. 2 records from Megafauna of the UKSRL exploration contract area and eastern Clarion-Clipperton Zone in the Pacific Ocean: Annelida, Arthropoda, Bryozoa, Chordata, Ctenophora, Mollusca. 5502 records from Propuesta para rescatar y conservar la paleobiota de la Cantera Tlayúa, en Tepexí de Rodríguez, Puebla: Fase II. 238 records from Données Mammifères marins Aquasearch - Dauphin Passion. 1 records from A new blind snake of the genus Letheobia (Serpentes: Typhlopidae) from Rwanda with redescriptions of L. gracilis (Sternfeld, 1910) and L. graueri (Sternfeld, 1912) and the introduction of a non-invasive preparation procedure for scanning electron microscopy in zoology. 3 records from A new species of the emesine assassin bug genus Emesopsis (Hemiptera: Heteroptera: Reduviidae) from Vietnam. 601 records from Muestreos y recolectas de flora endémica y casi-endémica de matorral costero y chaparral de la zona mediterránea Baja California, México. 20 records from Occurrence of mammalia relicts at site Niederlehme. 1264 records from Grand Voyeux - Suivis scientifiques. 135 records from Collection Polychaeta - ZSRO. 1 records from Reptilia ZMK. 16774 records from imr_mareano_rpsledge. 140 records from Données du/de la naturaliste LUPOLI ROLAND provenant de la base de donnée du SINP Île-de-France CETTIA. 4 records from Ensemble des données Orthoptères. 135 records from Allan Herbarium (CHR). 57007 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 1 records from A new species of iguanid lizard, genus Stenocercus (Squamata, Iguania), from the Central Andes in Peru. 24 records from Redescription of Hypostomus carinatus (Steindachner 1881) (Siluriformes: Loricariidae) from the rio Amazonas basin in Brazil. 2366 records from Cryoconite sediments Targeted Locus (Loci). 17 records from New species and records of the supertribe Stomatosematidi (Diptera: Cecidomyiidae) in Brazil. 65 records from Carabid Collection (Pinned Vouchers). 14314 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Invertebrates National Collection (MACNIn). 3697 records from Tasmanian Museum and Art Gallery provider for OZCAM. 636 records from TTRS Mammals. 148 records from Occurrence of mammalia relicts at site Veternica. 6 records from Neotropical Chvalaea Papp & Földvári (Diptera: Hybotidae: Ocydromiinae): new records, an illustrated key to species and description of three new species. 6 records from The neotropical stingless bee genus Nannotrigona Cockerell (Hymenoptera: Apidae: Meliponini): An illustrated key, notes on the types, and designation of lectotypes. 740 records from Monitoring data of marine turtles on the Togolese coast over 2012-2013 years. 4575 records from Narragansett Bay, RI Sediments Targeted Locus (Loci). 1 records from Genetic and morphological evidence for cryptic species in Macrobrachium australe and resurrection of M. ustulatum (Crustacea, Palaemonidae). 360 records from El complejo Brahea-Erythea (Palmae: Coryphoideae). 2892 records from Colección de Boraginales y Brassicaless del Museo Botánico CORD - IMBIV. 12 records from Three new taxa of the genus Cechetra Zolotuhin & Ryabov, 2012 (Lepidoptera, Sphingidae) from South-East Asia with notes on other species of the genus. 26 records from Synthèse de la Répartition des populations de mouflon corse en 2011 (réseau Ongulés sauvages ONCFS-FNC-FDC). 93662 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 936 records from Alterra (NL) - Microarthropods inventory in Dune vegetation. 1 records from Occurrence of mammalia relicts at site High Furlong. 58 records from Occurrence of mammalia relicts at site la Grotte des Eglises. 19 records from Marine metagenome ICM_CNE. 67 records from Einen Tag lang Forscher sein - Die 5c der Erich-Kästner-Schule erforscht das Bachemer Wiesental. 3704 records from Inventaire des pelouses calcicoles du PNR du Marais Poitevin 2017. 29 records from Systematics of the enigmatic South American Streblopus Van Lansberge, 1874 dung beetles and their transatlantic origin: a case study on the role of dispersal events in the biogeographical history of the Scarabaeinae (Coleoptera: Scarabaeidae). 227 records from Data on cetacean strandings (1999 - 2014) on the Ukrainian coast of the Black Sea and the Sea of Azov and adjoining areas. 1 records from Two new species of the bamboo-feeding planthopper genus Arcofacies Muir (Hemiptera: Fulgoroidea: Delphacidae) from China. 787 records from Programme ACT : Répartition Pie bavarde 2009 - 2013 Coordonnées GPS Lambert 93. 62 records from Tree-dwelling ant survey (Hymenoptera, Formicidae) in Mitaraka, French Guiana. 1095 records from Registros Primates Neotropicales Convocatoria APC. 3 records from On three new species of Elpidium Müller, 1880 and the re-description of Elpidium laesslei (Tressler, 1956) from Jamaica (Ostracoda: Podocopida: Limnocytheridae). 232 records from Borstgrasrasen um die Burg Baldenau im Oberen Dhrontal. 631 records from Anammox bacteria in sediment cores of Daya Bay, China. 13 records from Six new species of Macellicephala (Annelida: Polynoidae) from the Southern Ocean and south Atlantic with re-description of type species. 36 records from Schulgelände Lise Meitner Realschule (Paderborn). 111 records from Birdrace-Uhulogen-Lippe. 12 records from A new Bifidocoelotes species, with the description of the male of B. primus from Hong Kong, China (Agelenidae: Coelotinae). 1 records from First record of Gracixalus quyeti (Amphibia: Anura: Rhacophoridae) from Laos: molecular consistency versus morphological divergence between populations on western and eastern side of the Annamite Range. 7128 records from La familia Asclepiadaceae en México. 4 records from Revision of the genus Nybelinella (Teleostei, Bythitidae) with a new Atlantic, abyssal species. 8 records from DNA barcoding and morphological studies confirm the occurrence of three Atarbolana (Crustacea: Isopoda: Cirolanidae) species along the coastal zone of the Persian Gulf and Gulf of Oman. 136 records from Birdrace-SpeedBirder-Zwickauer_Land. 83 records from Birdrace-Die_Vogelscheuchen-Herford. 26 records from Four new species of Plega Navás, 1928 (Neuroptera: Mantispidae) from Mexico. 373 records from Otter survey of Ireland 2004 & 2005. 1055 records from Deep-water azooxanthellate Scleractinia from Vanuatu, and Wallis and Futuna Islands. 249 records from Données opportunistes produites par Alexandre RUFFONI dans le cadre de l’élaboration d’un guide de détermination des larves de plécoptères. 5 records from Two new day-flying species of Agrotis Ochsenheimer (Lepidoptera: Noctuidae) from the alpine summit of the Maunakea Volcano. 133152 records from Suivi Temporel des Rhopalocères de France (STERF). 15 records from New species of the genus Mimogonia and Holotrochus from South America (Coleoptera: Staphylindae: Osoriinae). 23 records from Australian Museum Ichthyology - 2012 Inscription Point. 2 records from Sinibotia lani, a new species of botiid loach (Teleostei: Botiidae) from Guangxi, China. 1552 records from Microbial diversity in shallow water hydrothermal sediments of Gueishan Island, Taiwan. 411 records from (Table 3) Abundance of planktonic foraminifera in ODP Hole 113-690C, large size fraction. 23 records from Landwehrbach. 20 records from On the systematic status of Isopericlimenaeus Marin, 2012 and its type species, Periclimenaeus gorgonidarum (Balss, 1913) (Crustacea: Decapoda Palaemonidae). 38 records from Revision of freshwater shrimps belonging to Caridina weberi complex (Crustacea: Decapoda: Atyidae) from Polynesia with discussion on their biogeography. 9781 records from CSIRO, fish surveys by the Soela, 1980s. 61 records from Alien Species in Poland - Plants. 323 records from Données de VINCENT Alexis (SAPROX). 22771 records from Vascular Plant Specimens of Yamagata Prefectural Museum. 979 records from Avifauna de bosques nublados en la cordillera Occidental, departamentos del Valle del Cauca, Risaralda y sur de Antioquia.. 13 records from A new species of genus Cyana Walker, 1854 (Lepidoptera: Erebidae: Arctiinae). 56 records from Données de la structure Forêts en Aulnoye provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from New taxonomic and faunistic data on Asian species of the genus Indenicmosoma Ardoin (Coleoptera: Tenebrionidae: Lagriinae), with description of a new species from Thailand. 8423 records from University Of Pretoria: Lacewing Database Project (1911-2015). 1 records from Description of the larva of Meliboeus morawitzi (Semenov, 1905) (Coleoptera: Buprestidae). 130 records from Synthèse de la Répartition des populations de bouquetin des alpes en 2005 (réseau Ongulés sauvages ONCFS-FNC-FDC). 1462 records from Avifauna en dos parches de bosque seco del departamento del Valle Cauca (Colombia). 1 records from Titanogryllus n. gen., the largest Gryllinae cricket from the Neotropical Region with three new species from the Brazilian Atlantic Forest (Orthoptera, Grylloidea, Gryllidae). 3350 records from The collection of Bathynellacea specimens of MNCN (CSIC) Madrid: microscope slices and DNA extracts. 168 records from Occurrence of mammalia relicts at site Geißenklösterle. 2 records from A cladistic approach for generic delimitation of Paracloeodes Day, Rivudiva Lugo-Ortiz & McCafferty, and Varipes Lugo-Ortiz & McCafferty (Ephemeroptera: Baetidae). 2349 records from Données naturalistes de Bernard Lalanne-Cassou. 78 records from Studies in Liocranidae (Araneae): a new afrotropical genus featuring a synapomorphy for the Cybaeodinae. 788 records from Fauna de coleópteros lamelicornios del Estado de Michoacán. Primera Fase: Subprovincia neovolcánica tarasca (Cuenca del Lago de Pátzcuaro) 1995-96. 1402 records from Données de collection de l'inventaire des Papillons de jour de Martinique. 7 records from Review of the Oriental and Palaearctic bee fly genus Euchariomyia Bigot (Diptera: Bombyliidae: Bombyliinae). 446 records from Programme ACT : Répartition Etourneau sansonnet 2006 - 2010 Coordonnées GPS Lambert 93. 3327 records from BioGIS - Mammals - SPNI. 21 records from New combinations, status, and species of Neotropical Ambrysini (Heteroptera: Naucoridae: Cryphocricinae). 90159 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Invertebrados. 29437 records from Inventaire et suivis d'espèces dans le Parc national des Cévennes. 50940 records from NOAA National Coral Reef Monitoring Program Benthic Percent Cover. 797 records from Área Galeras - Monitoreo de Aves, 2016. 2 records from First record of Trissolcus basalis (Hymenoptera: Scelionidae) parasitizing Halyomorpha halys (Hemiptera: Pentatomidae) in the United States. 163 records from Zostera noltei seagrass meadows spatial distribution at LTER site Ria de Aveiro lagoon in 2014. 395 records from Collection Echinodermata SMF. 4 records from A new species of large-bodied, tuberculate Hemidactylus Oken (Squamata: Gekkonidae) from the Eastern Ghats, India. 22 records from The fishery ground near Alexandria. XVI. Cumacea, stomatopoda, leptostraca by Adolf Steuer (1938).Notes and Memoirs No 26.. 2 records from Two new species of Picicola Clay & Meinertzhagen, 1938 (Phthiraptera: Philopteridae) from Piciformes (Bucconidae and Galbulidae) in Brazil. 19643 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 315 records from Scleractinia specimens of Kuroshio Biological Research Foundation. 625 records from Données araignées de Corse par Canard A., Rollard C., Villepoux O.. 1 records from A new species of king cricket Glaphyrosoma Brunner von Wattenwyl, 1888 (Orthoptera: Anostostomatidae: Glaphyrosomatini) from Costa Rica with behavioral observations. 6445 records from Nonindigenous Aquatic Species (NAS) Database Non-freshwater Specimens. 9741 records from marine sediment metagenome Raw sequence reads. 5 records from Molecular phylogeny reveals strong biogeographic signal and two new species in a Cape Biodiversity Hotspot endemic mini-radiation, the pygmy geckos (Gekkonidae: Goggia). 97 records from Amphibiens filet/Marbotte-Ronval 2013. 131125 records from Amphibiens et Reptiles de France (Enquête 2). 3320 records from Inventario de la biota marina (cnidarios, poliquetos, moluscos, crustáceos, equinodermos y peces) del Santuario Islas e Islotes de Bahía Chamela, Jalisco, México. 2933 records from Données naturalistes d'Alain BERLY. 8675 records from Insect Collection from the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 9 records from Two New Liocranid Species Records From Turkey (Araneae: Liocranidae). 116 records from Données opportunistes. 2240 records from (Figure 7) Distribution chart of benthic foraminifers in ODP Site 126-793. 222 records from The Deepwater Program: Northern Gulf of Mexico Continental Slope Habitat and Benthic Ecology - DgoMB: Fishs. 250 records from Inventaire et regroupement de données Natura 2000. 12719 records from Données bibliographiques et opportunistes Mammifères du Nord Pas-de-Calais issues du SIRF. 637617 records from Données de la flore d’Alsace (SBA). 77 records from Suivi naturaliste du Parc du Peuple de l'Herbe. 2 records from Pygmy grasshoppers of the genus Formosatettix Tinkhamı 1937 (Orthoptera: Tetrigidae: Tetriginae). 1 records from Two new Afrotropical genera of Scatopsidae (Diptera). 1606 records from Moluscos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRM-UV). 56 records from Données du/de la naturaliste Goncalves Cristina provenant de la base de donnée du SINP Île-de-France CETTIA. 872 records from Typotheca of the higher vascular plants stored in M.G. Popov Herbarium (NSK) at the Central Siberian botanical garden SB RAS. 696 records from the diversity of anammox bacteria in the subterranean estuary. 2 records from The new genus Habeastrum, with two new species (Gastropoda, Diplommatinidae) in Mato Grosso do Sul caves, Brazil. 165 records from Artenvielfalt auf den Elbwiesen (Dessau). 1009 records from Données naturalistes de Daniel PAVON. 976 records from GBIF: Nova Scotia Museum of Natural History - Freshwater mussels. 1275 records from Biodiversidad de productores primarios de las lagunas costeras del norte de Yucatán. 1 records from Redescription and biology of Gonatopus amazonicus Olmi (Hymenoptera, Dryinidae) from Southern Brazil. 2 records from Catalogue of distribution of lizards (Reptilia: Squamata) from the Brazilian Amazonia. III. Anguidae, Scincidae, Teiidae. 31 records from Bulletin d'informations de l'Association française de Lichénologie. 10075 records from Nematoda of Costa Rica (INBio). 4 records from A checklist of seed-beetles (Coleoptera: Chrysomelidae: Bruchinae) from Iran. 1494 records from EDP Foz Tua Nocturnal Birds - Ecological Monitoring Program [2011-2017]. 561 records from Fichas diagnósticas para 10 especies de anfibios y reptiles mexicanos. 421246 records from Cartografía de vegetación a escala de detalle 1:10.000 de la masa forestal de Andalucía. 192 records from "Ahrschleife bei Altenahr". 27334 records from South Australian Museum Australia provider for OZCAM. 2 records from Two new Thiratoscirtus species from Gabon (Araneae, Salticidae, Thiratoscirtinae). 2 records from Documenting diversity in the Amazonian butterfly genus Bia (Lepidoptera, Nymphalidae). 1 records from Occurrence of mammalia relicts at site Stockton-on-Tees. 11 records from Twenty more new species of Agrilus (Coleoptera: Buprestidae: Agrilinae) from the Oriental region. 220 records from (Table 1) Distribution of planktonic foraminifers in ODP Hole 126-787B. 6784 records from Whicher Scarp Flora Survey. 16 records from Biopearl expedition: SeaStars (Echinodermata, Asteroidea). 69 records from Unter hellen Zinnen und finsteren Grotten. 10 records from An annotated taxonomic checklist of the Neotropical Gracillariidae (Lepidoptera) with links to the information on host plants and parasitoids. 97 records from New species and records of deep-water Orbiniidae (Annelida, Polychaeta) from the Eastern Pacific continental slope, abyssal Pacific Ocean, and the South China Sea. 2 records from A taxonomic revision of the Western Palaearctic genus Cacochroa Heinemann 1870 (Lepidoptera, Depressariidae, Cryptolechiinae) with description of a new genus and a new species. 34 records from SPC PROCFish/C Fish Observations New Caledonia 2004. 10 records from Integrative taxonomy resuscitates two species in the Lasioglossum villosulum complex (Kirby, 1802) (Hymenoptera: Apoidea: Halictidae). 6433 records from Modernisation des ZNIEFF du PnrL. 1 records from A review of Garra (Teleostei: Cypriniformes) from two rivers in West Yunnan, China with description of a new species. 3 records from Taxonomic revision of the Afrotropical species of Pachyanthidium Friese (Hymenoptera: Megachilidae: Anthidiini). 60 records from Caracterización de la fauna reptiliana asociada a la cuenca del río Atrato, para el estudio de su navegabilidad, Quibdó - Chocó, 2012. 17 records from Feuchtwiese am Nationalpark-Haus Neuwerk. 324902 records from Estonian Nature Observations Database. 14 records from New and little known species of Halolaelaps (Acari: Mesostigmata: Halolaelapidae) from Ukraine. 14 records from New species of deep-water Calcigorgia gorgonians (Anthozoa: Octocorallia) from the Sea of Okhotsk, with a re-diagnosis and a taxonomic review of the genus. 52 records from Description of three new velvet geckos (Diplodactylidae: Oedura) from inland eastern Australia, and redescription of Oedura monilis De Vis. 38375 records from Botanical Museum, Copenhagen, Mycology Herbarium. 589 records from Birds (NMNO-BI). 7 records from Description of a new species of Moenkhausia (Characiformes: Characidae) from the upper Paraguay basin, Central Brazil, with comments on its phylogenetic relationships. 62 records from NCSM Mammals Collection. 1095 records from (Table 6) Distribution of planktonic foraminifers in ODP Site 112-684. 24 records from Taxonomic review of Epicadinus Simon, 1895 (Araneae: Thomisidae). 90 records from GEO-Tag mit der NAJU des Landkreises Ahrweiler am Bausenberg. 770 records from Nivå Bay species list, Zealand, Denmark. 122 records from Inventaire de la Flore patrimoniale dans la RNN Etang de Saint-Paul avant le 31/12/2017. 10 records from Colección de Entomología del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-E). 7 records from Taxonomic note on the oil-collecting bee Centris dimidiata (Olivier, 1789) (Hymenoptera: Apidae: Centridini). 4 records from Taxonomic update of the Neotropical genus Cryptocladocera Bezzi, 1923 (Diptera: Tachinidae), with remarks on tachinids with fissicorn antennae. 2 records from The discovery and description of a new species of Bent-toed Gecko of the Cyrtodactylus pulchellus complex (Squamata: Gekkonidae) from the Langkawi Archipelago, Kedah, Peninsular Malaysia. 6 records from New records, new genera, and new species in Acanthocinini (Lamiinae) from the Neotropical region, and new synonym in Cerambycinae (Coleoptera, Cerambycidae). 4207 records from CASES2003_2004. 376 records from Digitalización y sistematización de las colecciones biológicas del INECOL. 1103 records from Fife Nature Records Centre combined dataset. 48 records from CHAS Botany Collection (Arctos). 10 records from New records of species of the Polyonyx sinensis group (Crustacea: Decapoda: Anomura: Porcellanidae) from Japan, the Philippines, Singapore, and Malaysia, with descriptions of two new species. 237 records from Avifauna asociada a humedales urbanos del municipio de Quibdó - Chocó, 2019. 7 records from A new species of the genus Goera Stephens (Trichoptera, Goeridae) found in madicolous habitats in Amami-Oshima, southwestern Japan. 3 records from Refining the genus Rochinia A. Milne-Edwards, 1875: reinstatement of Scyramathia A. Milne-Edwards, 1880 and Anamathia Smith, 1885, and a new genus for Amathia crassa A. Milne-Edwards, 1879, with notes on its ontogeny (Crustacea: Brachyura: Epialtidae). 117 records from Naturschutzgebiet Lochbusch-Königswiesen. 19 records from Hiding in plain sight: rediscovery and review of Parygrus Erichson, 1847, with description of five new species from the Neotropics (Coleoptera: Byrrhoidea Dryopidae). 54 records from Revision of the ant genus Streblognathus (Hymenoptera: Formicidae: Ponerinae).. 6462 records from Odonata de Veracruz. 272 records from BIRDRACE Niederlausitz-Team. 65 records from A review of the genus Cyana Walker, 1854 from India, with descriptions of five new species and three new subspecies (Lepidoptera: Erebidae: Arctiinae: Lithosiini). 311 records from Línea base del medio biótico en los bosques dentro de la zona propuesta para Acuerdos de Conservación Voluntaria en la microcuenca de la Quebrada Aguazula - Rincón del Soldado_Yopal. 3609 records from British Antarctic (Terra Nova) Expedition, 1910-1913. 3 records from A new species of Isoperla (Plecoptera: Perlodidae) from the Qinling Mountains of northwestern China and notes on the Chinese species of the genus. 10386 records from Ice Wedge Polygon. 3714 records from Actualización de las bases de datos de colecciones, especies en peligro de extinción, colecta y propagación de germoplasma. 375 records from CG04_2017_12_18. 718 records from Données du/de la naturaliste CUENIN Sibylle provenant de la base de donnée du SINP Île-de-France CETTIA. 5 records from Two new species of the genus Leptoderes Serville, 1838 (Orthoptera, Tettigoniidae) from China. 247 records from Echinoidea distribution data from: Deep-sea fauna of European seas - an annotated species check-list of benthic invertebrates living deeper than 2000 m in the seas bordering Europe. 11 records from Collection Ephemeroptera - SMF. 530 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 146 (N.S) n° 39 (1), 2011 - Données faune. 10295 records from Données naturalistes d'Olivier GARGOMINY saisies sous cardObs. 242 records from FBIP: Identification of polychaetes used as bait. 8409 records from Denver Museum of Nature & Science - Entomology. 3 records from A new species of Athaumasta Hampson, 1906 (Lepidoptera, Noctuidae, Bryophilinae) from the Altai Mountains of Mongolia and China. 14557 records from Fish Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 16506 records from Database for alien invasive plants occurrences in Germany. 18 records from A new pygmy squid, Idiosepius hallami n. sp. (Cephalopoda: Idiosepiidae) from eastern Australia and elevation of the southern endemic ‘ notoides’ clade to a new genus, Xipholeptos n. gen.. 66 records from A revision of the grunter genus Syncomistes (Teleostei, Terapontidae, Syncomistes) with descriptions of seven new species from the Kimberley region, northwestern Australia. 1333 records from Crustacea Collection of Natural History Museum and Institute, Chiba. 1068 records from Trawl-survey data from the Pipeta programme in the Northern Adriatic Sea (Mediterranean) collected in 1988 and 1991. 8313 records from 成龍溼地鳥類生態紀錄. 1 records from Newly discovered sister lineage sheds light on early ant evolution. 7 records from A new species of Knodus (Characiformes: Characidae) from the Rio Cupari drainage, lower Rio Tapajós basin, Brazil. 2462 records from Waarneming.nl (NL) - Great Grey Shrike Count 2011-2012. 3673 records from Spider (NSMK-SP). 4125 records from OUPR - Herbário "Professor José Badini". 17 records from Descriptions of five new species of Homoplectra Ross (Trichoptera, Hydropsychidae) from Japan with reassignment of Homoplectra tohokuensis (Kobayashi). 57217 records from National Biodiversity Data Bank. Observation records, 1900-2014. 334 records from A taxonomic revision of the Formica rufibarbis Fabricius, 1793 group (Hymenoptera: Formicidae).. 596 records from Occurrence database of bryophytes and native animals of southern Chile. 83 records from VFD-H: Heidenrod: Pferdeweide Mürth. 12403 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase. 2 records from A new species of inseminating seasonal killifish of the Cynopoecilus melanotaenia complex from southern Brazil (Cyprinodontiformes: Rivulidae). 5 records from A new species of Aethiopella Handschin, 1942 (Collembola, Poduromorpha, Neanuridae) from Neotropical Region, with comments on the genus. 2 records from A new species of Yllenus Simon, 1868 from northern India (Araneae, Salticidae). 91 records from Nottekanal, Klasse 7 - 10. 54 records from A new Phoberus MacLeay species (Coleoptera: Scarabaeoidea: Trogidae) from the Maloti-Drakensberg Mountains of southern Africa and the Phoberus caffer species group reviewed. 10 records from Amoeboid protists isolated from ancient Siberian permafrost. 1 records from A new endemic insular Bent-toed Gecko (Squamata: Gekkonidae: Cyrtodctylus) from Quang Nam Province, Central Vietnam. 4733 records from Inventaire des Mollusques Sphaeriidae de France. 1 records from Swedish Malaise Trap Project (SMTP) - Bethylidae. 16885 records from données aranéologiques de CORNIC Jean-François. 742 records from Programme ACT : Répartition Alouette des champs 2000 - 2004 Coordonnées GPS Lambert 93. 86 records from Suivi de la flore patrimoniale de la RNR de Saint-Assise (77) dans le cadre d'un stage de M2. 54 records from Annotated checklist of the Dermaptera (Insecta) of French Guiana. 74 records from Données espèces - Expertise IPE 69. 1 records from A new species of Plestiodon (Squamata: Scincidae) from the Balsas Basin, Mexico. 2004 records from Inventario florístico en Baja California Sur: Región del Cabo e Islas adyacentes. 368 records from Tasmanian Museum and Art Gallery provider for OZCAM-Arthropoda. 678 records from (Table 2) Planktonic foraminiferal abundances in samples spanning the first appearance datum Globorotalia inflata at DSDP Hole 80-548. 6622 records from Données issues du dispositif de Biosurveillance des Retombées Atmosphériques Métalliques par les Mousses (BRAMM). 50 records from Flora und Fauna im Brexbachtal. 1653 records from MICROBIS database. 190 records from Herpetofauna laguna El Tinije. 2 records from Two new species of treefrog (Pelodrydidae: Litoria) from southern New Guinea elucidated by DNA barcoding. 123 records from Birdrace-Professorenteam-Münster. 14619 records from Ontario Breeding Bird Atlas 1981-1985. 6741 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos las Hermosas y Chilí-Barragán.. 3 records from A new species of Heliogomphus from Vietnam (Odonata: Gomphidae). 1648 records from Colección de Mamíferos del Instituto de Ciencias Naturales (ICN-MHN-Ma). 1 records from Two new earthworm species (Oligochaeta: Annelida) of the Orinoquia region of Colombia. 248680 records from Swiss National Orthoptera Databank. 391 records from Vegetación de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 23520 records from The Environmental Sample Collection of Spiders at the Staatliches Museum für Naturkunde Karlsruhe. 30091 records from BIOWIDE eDNA Fungi dataset. 35088 records from Computarización del Herbario ENCB. Fase I (Base de datos de los ejemplares del Valle de México). 1892 records from Weevil and Bark Beetle Recording Scheme - data verified via iRecord. 123 records from Caracterización hidrogeológica para el diagnóstico ambiental de alternativas del proyecto hidroeléctrico San Bartolomé (ISAGEN y HMV).. 3795 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Parque Natural Regional El Vinculo. 28 records from Nationalpark Harz Schul-AG Braunlage. 12844 records from Israeli Butterfly Monitoring Scheme (BMS-IL). 536 records from NEW-1. 140 records from Inventaire de la faune aviaire et de l'Ichtyofaune de la mare de l'Abarkaizé et des Oiseaux de Dan Saga. 4 records from Description of a new species of deep-water snake eel, Ophichthus mccoskeri (Ophichthidae: Ophichthinae) from Andaman Sea, India. 38 records from Was lebt in der Brutzwiese?. 2 records from Description of the male and larva of Schizomyia tuiuiu Urso- Guimarães & Amorim (Diptera, Cecidomyiidae), new records and a key to Neotropical species of Schizomyia Kieffer. 3 records from Biodiversity Surveys, South-east Arnhem Land. 1 records from A new species of Pyrrhosphodrus (Hemiptera: Heteroptera: Reduviidae) from the Caatinga ecosystem in Brazil, with notes on the genus. 626 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 144 (N.S) n° 37 (2), 2009 - Données faune. 18 records from Tejidos asociados al estado de conservación y riesgo de extinción del ensamblaje de anfibios de tres páramos colombianos. 179 records from Revision of the Ephippiochthonius complex in the Iberian Peninsula, Balearic Islands and Macaronesia, with proposed changes to the status of the Chthonius subgenera (Pseudoscorpiones, Chthoniidae). 1477 records from Inventaire des espèces végétales productives dans les Systèmes Agro-forestiers aux alentours de la Forêt classée de Ziama en Guinée Forestière (BID-AF2015-0066-REG). 201 records from BioAcoustica: Wildlife Sounds Database. 4 records from Discovery of the genus Kudakrumia Krombein, 1979 (Hymenoptera: Mutillidae) in India and description of a new species. 2154 records from Grasshopper and Cricket (Orthoptera) and related species records from Britain and Ireland to 2007. 5 records from Gewässeruntersuchung (Prien) mit Kl. 4b. 423 records from Programme ACT : Répartition Caille des blés 2008 - 2012 Coordonnées GPS Lambert 93. 7 records from Two new sponge-associated Branchiosyllis (Annelida: Syllidae: Syllinae) from Northeastern Brazil. 1139 records from SWECO. 4228 records from Données naturalistes de Loïc SALAUN. 3 records from A new species and new record of the genus Discoelius Latreille, 1809 (Hymenoptera Vespidae: Eumeninae) from China. 911 records from Programme ACT : Répartition Tourterelle turque 2003 - 2007 Coordonnées GPS Lambert 93. 13580 records from EDP Foz Tua: Terrestrial Birds (transects) - Ecological Monitoring Program [2009-2012]. 1555478 records from Flore Franco-Belge. 166 records from Programme ACT : Répartition Grive littorne 2002 - 2006 Coordonnées GPS Lambert 93. 16437 records from EAC - Herbário Prisco Bezerra. 2565 records from (Table 1) Distribution of early late Eocene fossil content in ODP Hole 115-715A. 2 records from A new species of Hemacroneuria and additions to Chinoperla (Plecoptera: Perlidae) from China. 4 records from Leif Richardson Vermont Bee Specimens. 63 records from The type specimens of bees (Hymenoptera, Apoidea) deposited in the Zoological Institute of the Russian Academy of Sciences, St. Petersburg. Contribution II. Family Halictidae, subfamilies Rophitinae, Nomiinae, and Nomioidinae. 9 records from PRA Sonneur à ventre jaune - étude de répartition. 8734 records from Collection Crustacea - ZMB. 682 records from Estudio herpetofaunístico de la Sierra Mazateca, Oaxaca, México. 4 records from Strepsiptera from Colombia: First record of the genus Strichotrema Hofeneder (Myrmecolacidae) and a new host-parasitoid association with Megalomyrmex cyendyra (Hymenoptera: Formicidae). 915 records from Estudio taxonómico del género Quercus (Fagaceae) en el Estado de México. 1 records from A new species of Notosacantha Chevrolat (Coleoptera: Chrysomelidae: Cassidinae) from Timor-Leste with a key to the Notosacantha vicaria - group. 19 records from Cordulegaster virginiae sp. nov. from Mexico, including a comparison with C. diadema Selys, 1868, and a redescription of its larva (Odonata: Cordulegastridae). 1 records from The crab spider genus Tarrocanus Simon, 1895 with notes on the genera Alcimochthes Simon, 1895 and Domatha Simon, 1895 (Araneae: Thomisidae). 14 records from Three new species of Alburnoides from the southern Black Sea basin (Teleostei: Cyprinidae). 1 records from Palaearctic species of Charipinae (Hymenoptera, Figitidae): two new species, synthesis and identification key. 8615 records from CSIRO, Tropical Zooplankton Biomass and Composition, Albatross Bay - Gulf of Carpentaria, North Australia 1986-1988. 2 records from Schistura epixenos, a new species of loach from the Nakai Plateau, Laos (Teleostei: Nemacheilidae). 1 records from Redescriptions of four Palaeotropical species of the cestode genus Notopentorchis Burt, 1938 (Cyclophyllidea: Paruterinidae). 143 records from Dermaptera in the icipe collection. 1153 records from ¿Existen especies de macroalgas o pastos marinos dentro del Golfo de California, que deban de estar consideradas dentro de la NOM (PROY-NOM-059-ECOL-2000)?. 25 records from Four new species and one new subspecies of Arctiinae (Lepidoptera: Erebidae) from the Tambopata river, Madre de Dios, Peru. 29 records from Review of the batfish genus Halicmetus Alcock, 1891 from Australian waters, with descriptions of two new species (Lophiiformes: Ogcocephalidae). 2 records from Checklist and distribution patterns of apoid wasps (Hymenoptera: Apoidea: Sphecidae and Crabronidae) of Cuba. 32660 records from The national database for marine data (MADS). 157 records from Programme ACT : Répartition Pigeon colombin 2008 - 2012 Coordonnées GPS Lambert 93. 2654 records from Patrols activities and fixed transect data collections of the fauna of the W biosphere reserve of Benin of 2017. 1 records from New collections of freshwater crabs from northern Madagascar, with the description of a new species of Foza Reed & Cumberlidge, 2006 (Brachyura, Potamonautidae), and comments on their conservation status. 4 records from First records of Kempnyia and Macrogynoplax (Plecoptera: Perlidae) from Tocantins State, Brazil with description of the immatures and the adult female. 19 records from Description of lithologic section units of IODP Hole 325-M0035A. 4 records from Four new species of Rhyacophila Pictet 1834 (Trichoptera: Rhyacophilidae) from Southeast Asia. 6 records from Revision of the Agrilus wittemani species - group (Coleoptera: Buprestidae: Agrilini) with description of three new species from India and Myanmar. 3 records from A new spider species, Heser stoevi sp. nov., from Turkmenistan (Araneae: Gnaphosidae). 13 records from Warnowufer Groß Klein. 3 records from On the diversity of Terebellides (Annelida, Trichobranchidae) in West Africa, seven new species and the redescription of T. africana Augener, 1918 stat. prom.. 198 records from (Table 4) Distribution of calcareous nannofossils at ODP Hole 125-785A. 16787 records from Sistemática e historia natural de algunos anfibios y reptiles de México. 1 records from BOTU-Fungi - Herbário Irina Delanova Gemtchújnicov - Coleção de Fungos. 11335 records from Diversidad de ocho grupos de insecta (Odonata, Lycidae, Phengodidae, Lampyridae, Cantharidae, Cerambycidae, Syrphidae y Vespidae) en tres regiones con bosque tropical caducifolio en México. 3444 records from (Table 2) Distribution of Cretaceous nannofossils at DSDP Hole 79-545. 237 records from Evaluación del ámbito hogareño y calidad de hábitat del borrego cimarrón (Ovis canadensis mexicana), Berrendo sonorense (Antilocarpa americana sonoriensis) y del Puma (Felis concolor) en la Reserva de la Biósfera El Pinacate y Gran Desierto de Altar. 44051 records from Alterra (NL) - Entomofauna inventory in peat swamps. 2 records from Modiolus cimbricus sp. nov. (Bivalvia: Mytilidae) endemic in the Kattegat-Skagerrak. 1 records from Taxonomic morphology of the genus Adineta (Rotifera: Bdelloidea: Adinetidae) with a new species from a suburban garden. 3 records from Immature stages and biology of the enigmatic oxyporine rove beetles, with new data on Oxyporus larvae from the Russian Far East (Coleoptera: Staphylinidae). 1 records from A new species of Aculus mite (Acari: Eriophyidae), a potential biocontrol agent for Australian swamp stonecrop, Crassula helmsii (Crassulaceae). 16 records from Valentin Moser Bats. 343 records from Programme ACT : Répartition Caille des blés 2012 - 2016 Coordonnées GPS Lambert 93. 807 records from Planktonic bacterial communities in the arctic Canada Basin and Kongsfjorden. 5 records from Gynacantha dryadula sp. nov. from the Guiana Shield (Odonata, Anisoptera: Aeshnidae). 2 records from Taxonomy of the genus Pristidia Deeleman-Reinhold, 2001 (Araneae: Clubionidae) in China. 17 records from New records of Cerambycidae (Coleoptera) for New Brunswick, Nova Scotia, and Prince Edward Island, Canada. 33560 records from Extracellular DNA marine sediment Targeted Locus (Loci). 384 records from "Schwarzwassertal" bei Pobershau. 2041 records from marine metagenome Targeted Locus (Loci). 1 records from Occurrence of mammalia relicts at site Ejstrup. 24493 records from Plan de vertebrados de la Patagonia. 1170 records from Springtales from lichen communities at Kollåsen in Norway. 3 records from Triplophysa sanduensis, a new loach species of nemacheilid (Teleostei: Cypriniformes) from South China. 5 records from On the genus Gastrodynerus Bohart, 1984 (Hymenoptera: Vespidae: Eumeninae). 3 records from Descriptions of species of Acrobeles von Linstow, 1877 (Nematoda, Rhabditida, Cephalobidae) from Kelso Dunes, Mojave National Preserve, California, USA. 3 records from Occurrence of mammalia relicts at site Igstadt I. 305345 records from Données acquises dans le cadre de l'activité du bureau d'étude BIOTOPE (1994 - 2013). 1 records from Reclustering the cluster flies (Diptera: Oestroidea, Polleniidae). 199 records from Distribution of Aphrocallistes beatrix in the N. Atlantic. 971 records from Danielsberg (Mölltal, Kärnten). 13000 records from LPO_PACA_2017_12_18. 583 records from Pachliopta butterfly specimens at Museum Zoologi Bogor, Indonesia. 43 records from Review of the Oxynoemacheilus tigris group with the description of two new species from the Euphrates drainage (Teleostei: Nemacheilidae). 6977 records from 2019_NSMK_PL_2. 1011 records from Programme ACT : Répartition Merle noir 2006 - 2010 Coordonnées GPS Lambert 93. 724 records from Programme ACT : Répartition Faisan commun 2009 - 2013 Coordonnées GPS Lambert 93. 1887 records from Foreign plant germplasm collections in Ghana. 64 records from (Table 4) Abundance distribution of the 'clavate' subspecies of the genus Globigerinelloides and Pseudoschackoina saundersi in the upper part of the Calabianca section. 6579 records from Computarización de la Colección de mamíferos del Centro de Investigaciones Biológicas del Noroeste SC. 333 records from (Table 4) Relative abundance of some planktonic foraminifera and fragmentation ratios for ODP Hole 117-728A samples. 1 records from Review of Cosmocomoidea (Hymenoptera: Mymaridae) from China, with descriptions of two new species. 620 records from GNOR-Projekt "Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert" und Umland. 1 records from Phylogeny of Corynoptera Winnertz and related genera, with the description of Claustropyga gen. nov. (Diptera, Sciaridae). 13845 records from Collection Pisces SMF. 1 records from Nomenclatural changes in the planthopper tribe Hemisphaeriini (Hemiptera: Fulgoromorpha: Issidae), with the description of a new genus and a new species. 1 records from The identity of Cicinnus orthane Blanchard, 1852 (Lepidoptera, Mimallonidae, Cicinninae), type species of Cicinnus Blanchard, 1852. 67 records from MEXU/Tipos de plantas vasculares. 3 records from On the identity of Cyphonoxia maljuzhenkoi Zaitzev, 1928 (Coleoptera Scarabaeidae: Melolonthinae). 12202 records from Pelagic Gulf of Mexico Targeted loci environmental. 30 records from Redescription of Bomis larvata L. Koch, 1874 with the description of a new Australian species. 4 records from Description of a new long-tailed skink (Scincidae: Trachylepis) from Angola and the Democratic Republic of the Congo. 4 records from Ctenodontina Enderlein, 1914 (Diptera, Asilidae, Asilinae): new combinations, synonyms, new species and new records for Argentina. 240 records from Landschaftspflegehof (Berlin). 7 records from Four new species of giant pill-millipedes from Vietnam (Sphaerotheriida, Zephroniidae). 210 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 146 (N.S) n° 39 (4), 2011 - Données faune. 9 records from Bachpatenschaft Beeke. 462 records from Données du/de la naturaliste Dodelin Benoît provenant de la base de donnée du SINP Île-de-France CETTIA. 167 records from SPC CoFish Invertebrates Observations Niue 2005. 16 records from Illustrated identification key to the genera of New World Micrelytrini (Hemiptera: Alydidae: Micrelytrinae), with description of two new genera, one new species and new distributional records. 22771 records from INVESTIGATING THE MICROBIAL EUKARYOTIC COMMUNITIES IN THE SURFACE WATERS OF THE ARAFURA SEA AND CORAL SEA. 1824 records from TransForest - vegetation, lichen and fungi data 2016. 3 records from Otacilia fansipan spec. nov., the second congener recorded from Vietnam (Arachnida: Araneae: Phrurolithidae). 126 records from Systematics, distribution and biology of the Australian ' micro-flea' wasps, Baeus spp. (Hymenoptera: Scelionidae): parasitoids of spider eggs.. 146 records from Monitoreo de la vegetación presente en la Cienaga de Beté, Municipio del Medio Atrato-Chocó, 2018. 10776 records from CEFS_16S_ITS. 36323 records from Biowide Species data. 11 records from Inventaire et regroupement de données Natura 2000. 1194 records from Actualización de la base de datos de crustáceos y registro de datos de peces del pacífico mexicano de la Colección Biológica de la Secretaría de Marina. 14 records from Correction of existing generic and species concepts in Platyceroidini (Coleoptera: Lucanidae: Lucaninae) and the description of four new species of Platyceroides Benesh. 8 records from Revision of the endemic Philippine Poeciloterpa Stål (Hemiptera: Cercopidae) with description of four new species. 521 records from Schanzenanlage Bergham. 1 records from A new riparian Mantidactylus (Brygoomantis) frog from the Tsaratanana and Manongarivo Massifs in northern Madagascar. 74 records from Reptiles de la expedición al Río Apaporis - Proyecto Colombia BIO. 24 records from The West Palaearctic Pseudodineura and Endophytus species (Hymenoptera, Tenthredinidae). 4 records from Distribution of Quinqueloculina sp. in sediment core 13200-025. 170 records from Crustacean specimens of Kitakyushu Museum of Natural History & Human History. 549 records from Données du Geckos vert des Hauts (Phesulma borbonica) du Parc national de La Réunion. 1 records from Southern distributional limits of Meliponini bees (Hymenoptera, Apidae) in the Neotropics: taxonomic notes and distribution of Plebeia droryana and P. emerinoides in Argentina. 25 records from On the Staphylinidae of the Greek island Samothraki (Insecta Coleoptera). 1 records from On the taxonomic status of the European Scolelepis (Scolelepis) squamata (Polychaeta: Spionidae), with description of a new species from southern Europe. 2 records from Two more new species of Hemiphyllodactylus Bleeker (Squamata: Gekkonidae) from the Shan Hills of eastern Myanmar (Burma). 8 records from Four new species of Diptilomiopinae from China (Acari: Eriophyoidea: Diptilomiopidae). 57 records from Schulgelände SGD/Viersen. 1533 records from Données du/de la naturaliste ARNABOLDI Frédéric provenant de la base de donnée du SINP Île-de-France CETTIA. 1305 records from Flora genérica de las gramíneas del estado de Tlaxcala. 7 records from Artenerhebung im Wiesenlautersystem/Pfälzerwald. 53 records from Leopard and Weddell seal program 1999/2002. 4708 records from Données naturalistes de Ségolène FAUSTEN. 53 records from Distribución, abundancia y efectos nocivos de tres especies de plantas invasoras. 2 records from Drepanosticta adenani sp. nov., from the Lanjak Entimau Wildlife Sanctuary in Sarawak (Odonata: Zygoptera: Platystictidae). 2 records from Microlepidogaster negomata, a new hypoptopomatine catfish (Loricariidae: Hypoptopomatinae) from Rio São Francisco basin, southeastern Brazil. 16 records from Invertebrates of the river Tana Basin in Kenya available at the National Museums of Kenya's Natural History Collections, Invertebrates Zoology Section. 352 records from Loup 2015 présence occasionnelle communale (réseau Loup-Lynx ONCFS). 72 records from Lebensraum Fluß/Zwickauer Mulde in Wolkenburg. 13940 records from Collection of Coleoptera. 11 records from Review of the genus Prays Hübner, 1825 (Lepidoptera: Praydidae) from China, with descriptions of twelve new species. 5 records from A new species of Pherbellia (Diptera: Sciomyzidae) from Iran. 1 records from Karpfenteich, Klasse 6d. 475 records from Rothschild Giraffe occurrence records observed at Mwea National Reserve in Central part of Kenya. 37 records from Revision of New World Cosmorrhyncha Meyrick, 1913 (Lepidoptera: Tortricidae: Olethreutinae), with descriptions of five new species. 2 records from Unveiling the morphology of the Oriental rare monotypic ant genus Opamyrma YAMANE, BUI & EGUCHI, 2008 (Hymenoptera: Formicidae: Leptanillinae) and its evolutionary implications, with first descriptions of the male, larva, tentorium, and sting apparatus. 1372 records from Formación de una base de datos de la biodiversidad de fauna marina y costera en el Golfo de California. 27 records from Ensemble des données Rhopalocères. 15 records from Monitoreo de Murciélagos en la Etapa de Ejecución de las Obras de Ampliación del EPF Floreña, Yopal, Casanare. 5576 records from uncultured prokaryote Targeted loci environmental. 3 records from Two new species of Garreta Janssens, 1940 (Coleoptera: Scarabaeidae: Scarabaeinae) from Southern Africa. 136 records from Inventaire faunistique de l'ENS des Parc des berges de Seine. 3435 records from Benthos Chirnov Basin 1986 and 2002. 84338 records from Queensland Museum provider for OZCAM. 6 records from A taxonomic reappraisal of the Smooth Slug Snake Asthenodipsas laevis (Boie, 1827) (Squamata: Pareidae) in Borneo with the description of two new species. 6387 records from Données naturalistes de Monsieur LAFAGE Denis. 5 records from On the genera Ptiloneura Enderlein, Loneura Navás, and Loneuroides García Aldrete (Psocodea: ‘ Psocoptera’: Ptiloneuridae). 133 records from Review of the Madagascan Orphninae (Coleoptera: Scarabaeidae) with a revision of the genus Triodontus Westwood. 1 records from Molche in Ruschwedel. 704 records from EDP Baixo Sabor: Herpetology – Baseline Studies [2009]. 9115 records from Données d'observations d'orthoptères en Auvergne, d'Emmanuel Boitier, de 1998 à 2015.. 6 records from Two new records and one new species of the genus Apelaunothrips from China (Thysanoptera: Phlaeothripidae). 701 records from Données naturalistes d'Arnaud LE NEVÉ. 1 records from A review of New World Malaxa (Hemiptera: Fulgoroidea: Delphacidae). 2141 records from University of Amsterdam (NL) - Páramo Vegetation Research, National Natural Park El Cocuy, Colombia. 178 records from Caracterización de algas y comunidad íctica de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 9 records from New species, new records, and new collection data of Rhyacophila from China (Trichoptera: Rhyacophilidae). 1 records from New Zealand forest-dwelling skinks of the Oligosoma oliveri (McCann) species-complex (Reptilia: Scincidae): reinstatement of O. pachysomaticum (Robb) and an assessment of historical distribution ranges. 163 records from Steinbruch Mainz-Weisenau, 3. Jahr. 1070 records from Museu Paraense Emílio Goeldi - Carcinológica Collection. 3251 records from Inventario florístico de la Sierra de Huautla, Morelos. 535 records from Inventario de sanguijuelas (Annelida: Clitellata Hirudinea) de México, con énfasis en las especies del centro de México. 1 records from A new species of Neoscelis Schoch from Mexico (Coleoptera: Scarabaeidae: Cetoniinae: Goliathini) with new distributional records for the genus. 69051 records from University of Michigan Museum of Zoology, Division of Reptiles & Amphibians. 3 records from New species of Graphocaecilius Enderlein (Psocodea: ‘ Psocoptera’: Lachesillidae) from Colombia. 5 records from Two new species of Guyruita Guadanucci et al., 2007 (Araneae, Theraphosidae) from Brazil. 1 records from A new species of Polyipnus (Stomiiformes: Sternoptychidae) from the Western South Pacific. 35 records from New species of Pyrrhulina (Teleostei: Characiformes: Lebiasinidae) from the eastern Amazon, Pará, Brazil. 368 records from Données du naturaliste PROVOST romain provenant de la base de donnée du SINP Île-de-France CETTIA. 13545 records from Temporal dynamics of bacterioplankton community in response to excessive nitrate loading in the oligotrophic coastal water. 90 records from Wildlife Sightings in the City of Logan. 8307 records from Birds Specimens. 58 records from Schulgelände Kranich-Gymnasium (Salzgitter). 468 records from Suivi de l'expansion du Frelon asiatique (Vespa velutina) : données espèces non cibles piégées. 1 records from A revision of the Anthaxia (Anthaxia) midas Kiesenwetter, 1857 species-group (Coleoptera: Buprestidae: Anthaxiini). 86 records from Fliegenhaupt Marksuhl. 66 records from Type specimens of invertebrate collection at University of Oulu Zoological Museum. 7758 records from DMNS Mammal Collection (Arctos). 1 records from A new species of the genus Pachytriton (Caudata: Salamandridae) from Hunan and Guangxi, southeastern China. 110 records from Occurrence of mammalia relicts at site Rejtek 1. 1 records from Culicoides Latreille biting midges (Diptera: Ceratopogonidae) of the Dongzhaigang mangrove forest, Hainan Province, China. 81 records from Taxonomic review of the ladybird genus Sticholotis from China (Coleoptera: Coccinellidae). 785 records from Colección de Mamíferos Marinos del Centro Nacional Patagónico. 989 records from IBF Monitoring of Fungi. 4 records from Phylogenetic differentiation and taxonomic consequences in the Saurodactylus brosseti species complex (Squamata: Sphaerodactylidae), with description of four new species. 1 records from A new species of Decomia Poppius from Laos and Thailand, with an annotated checklist and keys to genera and species of tribe Decomiini from Indochina (Hemiptera: Heteroptera: Miridae: Phylinae). 1809 records from BenthosChukchiFN762_1976_Falk5. 5 records from New data on jumping spiders of Iran, with a new species of Salticus (Araneae: Salticidae). 117 records from Programme de valorisation des zones humides chassées - volet Amphibiens. 10 records from Caracterización de flora, edafofauna epígea, anfibios y aves del Complejo de Páramos Pisba, Boyacá. 27 records from Caracterización floristica del Alto del Buey, Bahia Solano - Chocó. 1 records from Catalog of the Paramacronychiinae of China (Diptera: Sarcophagidae). 89 records from Seven new species of the spider genus Matta Crosby from caves in the State of Minas Gerais, Brazil (Araneae, Tetrablemmidae). 70 records from Données 2017 de l'Observatoire de la Biodiversité des Forêts. 236 records from Knechtweide (Kohlfurth). 3238 records from Butterflie Specimens of Yamaguchi prefectural Yamaguchi Museum. 90 records from MCP-Mamiferos - Coleção de Mamíferos. 96 records from The Echinoderm Fauna of the Azores (NE Atlantic Ocean). 358 records from Données du Syndicat de la Vallée de l'Orge Aval (SIVOA). 89 records from Meniscus Midges (Dixidae) of Ireland. 1017 records from Programme ACT : Répartition Merle noir 2001 - 2005 Coordonnées GPS Lambert 93. 1 records from A new deep-sea species of the caridean genus Bresilia Calman, 1896 (Crustacea: Decapoda: Bresiliidae) from Sagami Bay, central Japan. 171 records from Alien Species in Poland - Animals. 355 records from Occurrence database of native plants and animals of south-central Chile. 13 records from Three new species and three new records of the genus Bamboosiella from China (Thysanoptera: Phlaeothripidae). 259 records from Natura 2000 Parc naturel régional de Lorraine. 144284 records from Données de l'AFB acquises selon le protocole de pêche complète à un ou plusieurs passages. 10995 records from Census of the species of Benin. Data mobilized in the framework of JRS Benin project and funded by JRS Biodiversity Foundation. 3 records from Aradidae from Vietnam V. Bifurcatoaptera, a new genus of apterous Carventinae (Hemiptera: Heteroptera: Aradidae) from Vietnam. 610 records from Zambian Bat Collections Worldwide. 378 records from Rock ptarmigan (Lagopus muta) radio telemetry in Lierne, Norway. 146 records from Birdrace-Wannacks_Topti(c)ker-Lübeck. 270 records from Wald am Schloss Wittgenstein Bad Laasphe. 239 records from Shoreline fish distribution in Italian lakes assessed by electrofishing. 2 records from A new species of Zethus Fabricius (Hymenoptera, Vespidae, Zethinae) from Northeast Brazil, with notes on morphology and distributional records of Z. alessandroi Lopes. 26185 records from Données Mammifères Midi-Pyrénées enregistrées dans BazNat - Lot 1. 1428 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México, segunda etapa 2008-2009. 176 records from Paguroids (Decapoda: Anomura: Diogenidae and Paguridae) of the remote oceanic Archipelago Trindade and Martin Vaz, off southeast Brazil, with new records, description of three new species and zoogeographical notes. 1 records from Gaidropsarus mauli a new species of three-bearded rockling (Gadiformes, Gadidae) from the Lucky Strike hydrothermal vent field (Mid-Atlantic Ridge) and the Biscay Slope (Northeastern Atlantic). 4 records from Begonia henrilaportei Scherber. & J. Duruisseau (Begoniaceae), a new endemic species from the Masoala peninsula, Madagascar. 2 records from Two new species of Rhopalopsole (Plecoptera: Leuctridae) from China. 1 records from Cabdio crassus, a new species of cyprinid fish (Teleostei: Cyprinidae) from the Kaladan River of Mizoram, India. 39 records from Illustrated and online catalog of type specimens of freshwater fishes in the Colección de Peces Dulceacuícolas of Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P), Colombia. 59 records from Wichita State University Collection. 86 records from Données naturalistes de Pierre-Alexis RAULT. 376028 records from USGS Patuxent Wildlife Research Center Seabirds Compendium. 151 records from Levantamento da vegetação arbustiva do Parque Nacional do Jaú. 4 records from A new species of the fangblenny Adelotremus from Indonesia, with supplemental description of A. leptus (Teleostei: Blenniidae: Nemophini). 8158 records from Dark ocean microbial diversity. 10 records from A taxonomic revision of the Strumigenys nitens and simulans groups (Hymenoptera: Formicidae), two Caribbean radiations of leaf litter ants. 304 records from pbzt_insect_biodiversity. 3 records from Brasilisia n. gen. and Arraia n. gen., two new genera of Ocnerodrilidae (Annelida, Clitellata, Oligochaeta) from Eastern Amazonia, Brazil. 4 records from Three new species and one new record of Torrenticolidae (Acari, Hydrachnidia) from Wuyishan with an updated key for Chinese fauna. 22 records from Tanzanian Vertebrate Collection. 2 records from Ovomanonychus, a new genus of South American Sericoidini (Coleoptera Scarabaeidae: Melolonthinae). 3 records from DD_cyano Targeted loci environmental. 4 records from A new species of Thalerosphyrus Eaton 1881 (Ephemeroptera: Heptageniidae: Ecdyonurinae) from India. 15 records from Suivi de la colonie de Pipistrelles de la Petite Ceinture à Paris. 20 records from Riedkanal Bötzingen. 1 records from New record of the genus Baetiella Uéno, 1931 (Ephemeroptera: Baetidae) from India with description of a new species and new records for five species. 58 records from Données du/de la naturaliste Williamson Thomas provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from A new record of the family Isonychiidae (Insecta: Ephemeroptera) from the Western Ghats, India with a description of new species. 8 records from Revision Of The Australian Coccinellidae (Coleoptera). Genus Novius Mulsant Of Tribe Noviini. 11163 records from Programme FLASH : Répartition Pigeon ramier 2012 - 2016 Coordonnées GPS Lambert 93. 445 records from Enrichment metagenome. 19021 records from Diatomeas (Bacillariophyceae) y dinoflageladas (Dinophyceae) planctónicas más frecuentes en el Golfo de California. 82 records from Dragonfly records from the British Dragonfly Society's Dragonfly Recording Network for the period up to 2014. 1131 records from eDNA_Subseafloor. 2 records from A new species of Hypsohapsis (Heteroptera: Schizopteridae: Hypselosomatinae) from the Brazilian Amazon. 30 records from Inventario de vertebrados nativos en las islas Guadalupe, San Benito, Natividad, Asunción, San Roque, Isabel, Marietas, Socorro, Banco Chinchorro y Arrecife Alacranes. 6 records from Potamotrygon rex, a new species of Neotropical freshwater stingray (Chondrichthyes: Potamotrygonidae) from the middle and upper rio Tocantins, Brazil, closely allied to Potamotrygon henlei (Castelnau, 1855). 18 records from The genus Salfacarus (Acari: Opilioacarida) in Madagascar. 4 records from A Catalogue and Historical Study of the Odonata of Ecuador. 11 records from Códigos de barras de la vida en peces y zooplancton de México. 7 records from The publication of primary biological events in the international GBIF (Global Biodiversity Information Facility) network: A case study with a small dataset of field collected occurrence samples of Buriti palms (Mauritia flexuosa).. 39580 records from Herbarium Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 4 records from Two new species of Dentilabus Heinrich (Hymenoptera: Ichneumonidae: Ichneumoninae) from Japan and Korea, with redefinition of the genus. 10 records from Description of six new large species of Argentinomyia Lynch-Arribalzaga, 1891 and redescription of Talahua fervida (Fluke, 1945) (Diptera, Syrphidae, Syrphinae). 5 records from Loricifera - SMF. 13 records from Rhaphium (Diptera: Dolichopodidae: Rhaphiinae) from China with six new species. 667 records from Antarctic Krill occurrence data from Discovery expeditions. 833 records from Plant species from the sacred and community forests of Mono departement. 479121 records from KTP Ring Data. 1 records from Two new species of Darnini (Hemiptera: Membracidae) from Colombia and Peru. 4 records from Pseudotibiozus Demange, 1970 - millipedes of the Eastern Arc Mountains, Tanzania (Diplopoda, Spirostreptida, Spirostreptidae). 11 records from Données d'observation opportunistes collectées durant la campagne de prélèvements sédimentaires SHELL/CREOCEAN en Guyane française en 2013. Shell Exploration and Production France. 2252 records from Synthèse de la Répartition des populations de cerf élaphe en 2000 (réseau Ongulés sauvages ONCFS-FNC-FDC). 1 records from The identity of Parandra laevis Latreille, 1804 and nomenclatural changes in the Parandrinae (Coleoptera, Cerambycidae). 12118 records from Soil metagenome from healthy and unhealthy agricultural soil. 1478 records from Programme FLASH : Répartition Pluvier doré 2012 - 2016 Coordonnées GPS Lambert 93. 41 records from Morphologische Daten von Natrix. 3 records from A new species of Ahaetulla Link, 1807 (Serpentes: Colubridae: Ahaetullinae) from India. 46 records from Revision of the Garra species of the Hajar Mountains in Oman and the United Arab Emirates with the description of two new species (Teleostei: Cyprinidae). 103 records from Collection botanique Lamy de la Chapelle E. (BOUM). 2977 records from Brown University Herbarium. 89 records from Données du/de la naturaliste Le baron Gaetan provenant de la base de donnée du SINP Île-de-France CETTIA. 186 records from Caracterización biológica de la ventana de biodiversidad Montes de María, Municipio de Colosó, Sucre, Colombia. 95 records from BIRDRACE accipiter hardcore birding. 19339 records from Inventaire de la flore des Pyrénées-Atlantiques 2017 - Littoral. 89 records from Occurrence of mammalia relicts at site Spitzbubenhöhle. 112 records from Marine Mammal Observation - Total E&P Angola 2006-2011. 1 records from Orbinia wui, a new species from China, with redescription of O. dicrochaeta Wu, 1962 (Annelida, Orbiniidae). 23 records from A revision of Eastern Palaearctic Anthobium Leach, 1819 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini). II. fusculum group, and two additional species of the nigrum group. 17 records from The millipede genus Glomeris Latreille, 1802 (Diplopoda, Glomerida, Glomeridae) in North Africa. 1 records from A new genus and species of entocytherid ostracod (Ostracoda: Entocytheridae) from the John Day River Basin of Oregon, U. S. A., with a key to genera of the subfamily Entocytherinae. 58 records from LISU Herbario Angola. 2 records from Intraspecific variation in adult Uvitellina iraquensis Dronen, Ali & Al-Amura, 2013 (Cyclocoelidae: Haematotrephinae) from two collection sites of white-tailed lapwing, Vanellus leucurus (Lichtenstein) (Charadriiformes: Charadriidae), in Iraq. 229 records from Distribución y estructura poblacional de la tortuga de Berlandier, (Gopherus [=Xerobates] berlandieri) en México. 24 records from RNF - Données de la Réserve Naturelle du Marais de Lavours. 1 records from Swedish Malaise Trap Project (SMTP) - Heloridae. 7582 records from Tropical epiphyte diversity under human impact ? Comparing primary forests, secondary forests, and forest fragments in Ecuador - Otonga. 2 records from A new ant species of the Leptogenys sulcinodagroup (Hymenoptera: Formicidae) from Saudi Arabia. 4 records from Pheronema on the mid-Atlantic Ridge, data from NRCan. 82750 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 3 records from Metrocoris sikkimensis sp. nov. (Hemiptera: Heteroptera: Gerridae) from northeastern India, with a key to species of the compar group occurring in India. 6651 records from Données naturalistes de LUPOLI Roland. 68 records from Données du/de la naturaliste JOSSERAND oriane provenant de la base de donnée du SINP Île-de-France CETTIA. 9 records from The Maugean Skate, Zearaja maugeana sp. nov. (Rajiformes: Rajidae) - a micro-endemic, Gondwanan relict from Tasmanian estuaries.. 2 records from Two new species of stargazers of the genus Uranoscopus (Teleostei: Uranoscopidae) from the western Pacific Ocean. 355 records from Données naturalistes de François BRETON. 8 records from Rare And New For The Fauna Of The Russian Far East Spiders (Aranei). 1 records from A new species of Lepidodactylus (Reptilia: Squamata: Gekkonidae) from the Kei Islands, Maluku, Indonesia. 20 records from Phytoplankton abundance in the Wadden Sea off List, Sylt, North Sea in 2004. 5 records from Copepoda (Siphonostomatoida: Dirivultidae) from Hydrothermal Vent Fields on the Central Indian Ridge, Indian Ocean. 23940 records from EDP Foz Tua: Terrestrial Birds, Winter (point counts) - Ecological Monitoring Program [2011-2017]. 12 records from Lepidoptera specimen database of Japan. 164362 records from DFO Maritimes Research Vessel Trawl Surveys Fish Observations. 5640 records from Solenosmilia matrix annotations and VME habitat identification in video from voyage IN2018_V06, Australia (2018). 3857 records from Collection Vermes - ZMB. 130 records from BIRDRACE - The famous Grouse feat. The James. 2 records from Baetis pentaphyllus sp. nov., a new species of mayfly (Ephemeroptera: Baetidae) from the Russian Far East. 115 records from Aves de la expedición en el páramo El Valle, Boyacá - Proyecto Boyacá BIO. 372 records from Recursos hidrobiológicos de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 2 records from Taxonomic review of the genus Compsiluroides Mesnil (Diptera: Tachinidae), with the description of a new species. 144 records from Diet, Tidal and Vertical Variations of Phytoplankton and Its Environment in Frobisher Bay, Canada, 1980 and 1981. 6 records from Taxonomic changes of some neotropical species of Arctiini Leach (Lepidoptera: Erebidae: Arctiinae). 1 records from A new species of Creagrutus (Characidae: Stevardiinae) from the upper Río Magdalena, Colombia. 52 records from Occurrence of mammalia relicts at site Goyet Cave 3. 74 records from Anfibiofauna asociada a la quebrada Giginia, corregimiento de Doña Josefa, Municipio del Atrato - Chocó, 2019. 37 records from FBIP: scallop population genetics. 18 records from Schulgarten der Gesamtschule Am Heidberg. 2091 records from Museu Paraense Emílio Goeldi - Opiliones Collection. 1270 records from Données du/de la naturaliste Lantz André provenant de la base de donnée du SINP Île-de-France CETTIA. 68 records from Gewässer des Wartbergparks Stuttgart (bei der Ökostation der VHS Stuttgart). 5 records from Inventur der Natur rund ums NABU-Naturzentrum in Haseldorf. 4 records from Society Islands beach bum black flies (Diptera: Simuliidae). 5496 records from Abondances et caractéristiques biologiques des juvéniles de saumons échantillonnés lors des indices d'abondance du saumon dans la rivière Nivelle (France). 2723 records from Computarización de material complementario en la Colección Regional de Invertebrados del Pacífico mexicano, Instituto de Ciencias del Mar y Limnología, Unidad Académica Mazatlán, UNAM. 62 records from Données naturalistes de BONCHE Jérôme. 304 records from Base de datos de fauna batial, abisopelágica y abisal del Golfo de México. 32 records from Abyssal fauna of the UK-1 polymetallic nodule exploration claim, Clarion-Clipperton Zone, central Pacific Ocean: Echinodermata. 8985 records from Universidad de Murcia, Dpto. Biología Vegetal (Botánica), Murcia: MUB-MUSCI. 9 records from Character state variation within Dendrothrips (Thysanoptera: Thripidae) with a revision of the species from China. 3369 records from Hormigas del Museo de Entomología de la Universidad del Valle. 29 records from Reptiles Specimens of Akita Prefectural Museum. 256 records from Electron Micrograph Database - Terrestrial and Limnetic Specimens. 5276 records from Biodiversidad de la Sierra Tarahumara. Lepidoptera: Mimallonoidea, Lasiocampoidea, Bombycoidea y Pyraloidea. 159 records from Tejidos colectados en el piedemonte llanero, Boyacá - Proyecto Boyacá BIO. 144 records from Biodiversity survey of Rugezi wetland, Year 2013. 449 records from Artsprosjekt Pyrenomycetes. 3 records from Crustáceos del municipio Santa Bárbara, Santander - Proyecto Santander BIO. 121 records from Etude écologique du Parc des Lilas (94). 12 records from Données bibliographiques ASFRA. 1 records from Brachiopods Specimens of Akita Prefectural Museum. 7953 records from (Table 2) Distribution of late Miocene to Pleistocene calcareous nannofossils in ODP Hole 105-646B. 16 records from Notes on the Dianous aereus complex with description of a new species (Coleoptera, Staphylinidae). 24 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-5. 1 records from A new Aceria species (Acari: Prostigmata: Eriophyoidea) from Minuartia frutescens (Caryophyllaceae) in Hungary. 430 records from Archaeal diversity of surface seawater (A3,A5,G3,G5) Targeted Locus (Loci). 173 records from Renaturierung Werse (Innenbereich Beckum). 7505 records from Base de datos de las gramíneas (Poaceae) del noreste de México. 10986 records from FUEL - Herbário da Universidade Estadual de Londrina. 3971 records from Inventario de larvas de peces en la región sur del Golfo de California (GAP 81, 85 y 86) y en el Pacífico Tropical Mexicano (GAP 88-91). 4722 records from Dataflos. 3 records from A new species of Flavoperla Chu, 1929 (Plecoptera: Perlidae) from Guangxi Zhuang Autonomous Region of southern China. 2743 records from marine sediment metagenome Raw sequence reads. 9 records from The cicada genus Procollina Metcalf, 1952 (Hemiptera: Cicadidae): redescription including fourteen new species, with a key to the species of the subtribe Dazina Kato, 1932 rev. stat., the description of the Aragualnini n. tribe, and one new combination. 20191 records from Seabirds in Norway - Estimated population sizes. 1470 records from Institut Menorquí d'Estudis. Herbarium Generale Minoricae: HGM. 55 records from Occurrence of mammalia relicts at site Rusenschloß. 4803 records from Photographs of higher plants, mosses, fungi, lichens, and algae. 1135 records from Tejidos de ejemplares colectados en el Páramo de Chingaza - Proyecto Colombia Bio. 2 records from Two new species of Spider Wasps (Hymenoptera, Pompilidae), Ctenagenia pagliano from Lebanon and Evagetes liane from Canary Islands. 4 records from South Lanarkshire peatland records 2013. 11 records from A new genus and five new species of Anostostomatidae from the Lesser Antilles (Orthoptera: Ensifera). 83 records from Données du/de la naturaliste GAUTHIER Nicolas provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from First report of the old world genus Pelecystola in North America, with description of a new species (Lepidoptera, Tineidae). 682 records from Transferts SI Faune - Données naturalistes opportunistes de Cedric DEVILLEGER. 2 records from Two new species of the genus Daptonema Cobb, 1920 (Nematoda: Xyalidae) found in an intertidal seagrass bed on the coast of the Andaman Sea, Thailand, with reference to the taxonomic status of the genus Trichotheristus Wieser, 1956. 1 records from A new, peculiar genus of Cossoninae (Coleoptera, Curculionidae) from Oman with description of a new species, larva and notes on biology. 15251 records from Universidad Autónoma de Madrid, Madrid; Lepidópteros. 40738 records from Herbarium Specimens of Tokushima Prefectural Museum, Japan. 1 records from Diversity of methyl alkyl succinate synthase genes in hydrocarbon seep sediments (Raw sequence reads). 30 records from New distributional records of Staphylinina in Taiwan, including a new species of Miobdelus Sharp (Coleoptera: Staphylinidae: Staphylininae: Staphylinini). 1 records from Labrys khuzestanensis n. sp. (Nematoda, Tylenchidae), a new member of the genus with large labial plate. 13 records from Lane 6 Analysis. 3939 records from Census of plant species in Pahou forest reserve. 3 records from A new species of Capnia (Plecoptera: Capniidae) from Lesser Khingan Range (Amur River Basin, Far East of Russia). 6 records from Pauximyia, a new genus of Odiniidae (Diptera: Acalyptratae) with description of two new species from Brazil. 368 records from Lillachtal mit Kalktuffquelle bei Weißenohe. 28 records from Lepidurus arcticus survey Northeast Greenland 2013. 151 records from VSN-Wiese. 2 records from A new species of Liriomyza Mik (Diptera, Agromyzidae) on okra in Brazil. 6578 records from Ibaraki Nature Museum, Fungi collection. 1298 records from Colección de Reptiles - Museo de Herpetología de la Universidad de Antioquia. 93324 records from Amis_des_Marais_du_Vigueirat_2017_12_18. 49 records from Atelier Malacologie continentale, 14-15septembre, La Flèche (Sarthe). CEN Pays de la Loire. 14 records from A new species of long-legged terrestrial Terrapotamon Ng, 1986 (Crustacea: Brachyura: Potamidae) from limestone formations in Satun, southern Thailand. 20442 records from Trondheim urban biodyversity survey. 94 records from Données du/de la naturaliste LUSTRAT Philippe provenant de la base de donnée du SINP Île-de-France CETTIA. 6 records from Swedish Malaise Trap Project (SMTP) - Banchini. 89 records from Taxonomy and molecular phylogeny of the Platystictidae of Sri Lanka (Insecta: Odonata). 20796 records from R. L. McGregor Herbarium Lichen Collection. 217 records from Coleção de Bryozoa do Museu Nacional - UFRJ. 8572 records from UAM Fish Collection (Arctos). 8808 records from Survey of bumblebees in central Alberta - 2018. 2 records from New data on the taxonomy and distribution of Philippine Ochodaeidae and description of a new species from Central Visayas (Coleoptera: Scarabaeoidea). 30 records from Bird Specimens of The Cattle Museum. 23 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Reptilia (ZUFMS-REP). 331 records from KARSTLANDSCHAFT SÜDHARZ - VOM GIPSABBAU BEDROHT (Grenzstreifen am Röseberg). 4 records from New data on the Pterophoridae fauna of Liberia (Lepidoptera: Pterophoridae). 2 records from A new species of the genus Microhyla Tschudi, 1838 (Amphibia: Anura: Microhylidae) from Tay Nguyen Plateau, Central Vietnam. 150 records from Selztal bei Friesenheim. 32603 records from Banded Iron Formation and Greenstone survey data. 563 records from UCM Mammal Collection (Arctos). 1161 records from (Figure 4) Distribution chart of benthic foraminifers in ODP Site 126-791. 173 records from Natural History Museum, Vienna - Herbarium W. 281250 records from Quadrige. 21 records from New species and records of Leuctridae (Plecoptera) from Guangxi, China, on the basis of morphological and molecular data, with emphasis on Rhopalopsole. 67 records from (Table 1.2.1.1) Abundance of sympagic meiofauna of sea-ice core PS69/549-2. 46 records from Schulgelände (Wetter). 278 records from Deponie Klausdorf. 2 records from Hangzhou-sediment-sample Raw sequence reads. 1 records from The genus Zelurus Hahn, 1826, in Brazilian caves: description of new species and comments on the potential distribution of the genus in South America. 14 records from A new freshwater shrimp species of the genus Palaemon Weber, 1795 (Decapoda: Caridea: Palaemonidae) from northeastern Japan. 144 records from BIRDRACE Punkbirder Helgoland. 277 records from Inventario de gasterópodos terrestres y dulceacuícolas del área focal de Ixcan, Chiapas. 36 records from Lynx 1992 présence Régulière Mailles 10km Réseau Loup-Lynx ONCFS. 4 records from A new species of the greeneye genus Chlorophthalmus (Teleostei: Chlorophthalmidae) from the central North Pacific. 3 records from Campydoroides manautei gen. et sp. nov. from New Caledonia and a reappraisal of the suborder Campydorina (Nematoda). 6 records from Four new crane fly species of subgenus Tipula (Vestiplex) (Diptera, Tipulidae) from China. 2 records from Swedish Malaise Trap Project (SMTP) - Mycetophilidae, Keroplatidae. 2 records from More cautionary tales: family, generic and species synonymies of recently published taxa of ghost and mud shrimps (Decapoda: Axiidea and Gebiidea). 1715 records from Helmintos parásitos de peces del sureste de México. 383 records from Inventario de Peces del SFF Isla Malpelo, Proyecto Colombia Bio. 2 records from Cnemaspis rajakarunai sp. nov., a rock dwelling day-gecko (Sauria: Gekkonidae: Cnemaspis) from Salgala, an unprotected lowland rainforest in Sri Lanka. 61 records from Naturpark Kottenforst-Ville 15.6.09. 3 records from A new species of Neobathyclupea from the northern Indian Ocean with comments on N. malayana (Teleostei, Perciformes, Bathyclupeidae). 1 records from Two new species of Plutomurus Yosii (Collembola, Tomoceridae) from the Caucasus. 3 records from Euhampsonia rubricata spec. nov., a new moth species from northeastern India and western Myanmar (Lepidoptera: Notodontidae). 173 records from FFH-Gebiet Klosterwasser/Burkau. 81 records from BCCM/ULC Cyanobacteria culture collection at the University of Liège (ISO9001 certified). 7 records from A new species of poison-dart frog (Anura: Dendrobatidae) from Manu province, Amazon region of southeastern Peru, with notes on its natural history, bioacoustics, phylogenetics, and recommended conservation status. 353 records from Données naturalistes de Hubert GUIMIER. 1807 records from Données naturalistes de Hervé BOUYON. 1800 records from Données de la collection Rousset -1947-2013. 2 records from Revision of the genus Systellapha Enderlein (Micropezidae, Taeniapterinae). 10 records from Ten new species of the spider genus Pholcus Walckenaer, 1805 (Araneae, Pholcidae) from Southeast Asia. 399 records from (Table 2) Distribution of recurrent planktonic foraminifera at DSDP Hole 75-530A. 874 records from Programme ACT : Répartition Grive musicienne 2004 - 2008 Coordonnées GPS Lambert 93. 134 records from Lynx 2005 présence Occasionnelle Mailles 10km Réseau Loup-Lynx ONCFS. 87 records from Review of some species groups of the genus Oospila Warren, with descriptions of nine new species (Lepidoptera: Geometridae: Geometrinae). 12094 records from Amino acid addition experiment Metagenome. 3131 records from Données DREAL Centre-Val de Loire - Faune - 2018. 1170 records from Tetraonid line transect surveys from Norway: Data from Fjellstyrene. 1288 records from Comparative metagenome analysis of normal and arsenic contaminated soils from ballia district, Uttar Pradesh, India. 33 records from Pseudoscorpiones Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 2 records from Description of a new species of Euptychiina (Lepidoptera: Nymphalidae: Satyrinae) from South America. 9349 records from Harriet Irving Botanical Gardens (HIBG). 44459 records from Weed and native flora data for the Swan Coastal Plain. 9002 records from Uncultured Environmental Isolate Targeted loci environmental. 4128 records from RNF - Données du Parc Naturel Régional du Vercors. 45 records from Crustacea specimens of Kuroshio Biological Research Foundation. 3079 records from Insectes Hyménoptères Scollidés de France. 1951 records from Family Geraniaceae in CSBG SB RAS herbarium collections (NS, NSK). 1 records from First description of the male of the type species Meotipa picturata Simon, 1895 and description of a new Meotipa species (Araneae, Theridiidae) from India. 4717 records from Weddell Sea macrozoobenthos EASIZ I. 2526 records from sea water Picoeukaryotic Community Raw sequence reads Raw sequence reads. 13 records from A new species of Leptolalax (Anura: Megophryidae) from northern Vietnam. 1338 records from Fauna y flora en áreas con cultivos de palma de aceite en el norte y oriente de Colombia. 2099 records from Communauté_de_communes_Asse_Bléone_Verdon_2017_12_18. 14 records from Occurrence of mammalia relicts at site Climauti II. 10389 records from Seawater metagenome Targeted loci environmental. 135 records from Waldi-Weiher. 459 records from Gewann Krampf (Heilbronn). 4 records from On new or poorly known Australian Filistatidae spiders (Araneae: Araneomorphae), including a study on the fine morphology of Wandella. 74 records from Naturschutzgebiet Lippeaue (Marl) - Pfadis in Sickingmühle. 25 records from Données de NICOLAS Vincent (SAPROX). 607 records from Inventory of Bassila forest (North-Benin). 29 records from Hydroids of the BANZARE Antarctic expeditions 1929 - 1931. 1013 records from Circumpolar Seabird Monitoring Plan. 1 records from Rhopalomenia glandulosa spec. nov., and the restoration of Entonomenia Leloup (Mollusca: Solenogastres). 6440 records from Microbial ecology of bacteiral community in sediment from adjacent waters of Rushan Bay. 3 records from The larva of Lestes alfonsoi Gonzalez & Novelo (Zygoptera: Lestidae). 2 records from Revision of Terellia amberboae group of species (Diptera: Tephritidae). 2572 records from seawater metagenome Metagenome. 2436 records from Diet results from Adelie penguins at Bechervaise Island and Whitney Point, 2012/13. 56 records from Heliconiine Butterfly Collection Records from University of Cambridge. 5 records from A New Southern Caribbean Species of Angel Shark (Chondrichthyes, Squaliformes, Squatinidae), Including Phylogeny and Tempo of Diversification of American Species. 943 records from Programme ACT : Répartition Tourterelle turque 2012 - 2016 Coordonnées GPS Lambert 93. 6 records from (Table 1) Nesting characteristics of greater snow geese (Chen caerulescens atlanticus) on Bylot Island between 1995-2005. 4 records from Determinación de la clase Reptilia presente en el corregimiento de Juanchaco, Valle del Cauca, Colombia para el mes de Septiembre de 2017. 357 records from (Table 2) Species density and composition of an inshore and offshore station in Kongsfjord, Svalbard. 79 records from Birdrace-Bielefinken-Bielefeld. 4054 records from Fish specimens of Toyama Science Museum. 342 records from Kenai National Wildlife Refuge, Alaska (KNWR) Insect specimens (Arctos). 107 records from Müritz-Nationalpark. 86 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-2. 5987 records from Colección Limnológica Universidad de Antioquia. 22 records from Kuhwiese Beerentaltrift (Hamburg/ Harburg). 2 records from A new species of Polyamia DeLong (Hemiptera: Cicadellidae: Deltocephalinae: Deltocephalini) representing the first record of the genus from South America. 2377 records from Establecimiento de un área protegida en el Alto y Bajo Calima, área clave de biodiversidad en el Valle del Cauca, Colombia. 14391 records from Enquête Lucane. 947 records from Erlengraben/Lipp-Tal (Östringen). 874 records from CSIC-Real Jardín Botánico-Colección de Algas (MA-Algae). 1986 records from Observations de Coléoptères saproxyliques de Frédéric LACOSTE. 27901 records from Birds of Rottnest Island, Western Australia, 1981 - 2007. 2860 records from Colección de Alismatales, Apiales, Aquifoliales, Arecales y Asparagales del Museo Botánico CORD - IMBIV. 2 records from The species of Ctenopelma Holmgren (Hymenoptera, Ichneumonidae) from China. 2 records from A new species of the genus Diogenes Dana, 1851 (Crustacea: Decapoda: Anomura: Diogenidae) from Gujarat, northwestern India. 392 records from Expédition Karubenthos 2012 : inventaire des Echinodermes de la Guadeloupe. 1 records from New species of Neohybos Ale-Rocha & Carvalho (Diptera, Hybotidae, Hybotinae) from South America. 2548 records from BioGIS - Reptiles - HUJ collections. 214395 records from Flora Atlas N.T.. 5216 records from E1 Targeted Locus (Loci). 1 records from Klosterlandschaft Maulbronn 19. und 20. Juni 2010. 4156 records from Fishes in the Argentine Sea from 1967 to the present time. 3 records from Redescription of Cletocamptus albuquerquensis and C. dominicanus (Harpacticoida: Canthocamptidae incertae sedis), and description of two new species from the US Virgin Islands and Bonaire. 55 records from Ours 2007 présence Occasionnelle Mailles 10km LAEA Réseau Ours brun ONCFS. 3 records from A new species of Dohrnemesa from Brazil, with notes on the male of D. carvalhoi and on D. albuquerquei (Hemiptera: Heteroptera: Reduviidae: Emesinae). 2 records from Two new species in the genus Andronymus Holland, 1896 (Lepidoptera, Hesperiidae). 2 records from Two new species of Hetereleotris (Perciformes: Gobiidae) from the Red Sea. 829 records from Données de la structure SNPN - Société Nationale de Protection de la nature provenant de la base de donnée du SINP Île-de-France CETTIA. 845 records from Alterra (NL) - Entomofauna inventory in arable fields Hoeksche Waard. 129 records from Données du/de la naturaliste jourdan christian provenant de la base de donnée du SINP Île-de-France CETTIA. 147 records from Revision of the spider genus Hoplopholcus Kulczyński (Araneae, Pholcidae). 754 records from Programme ACT : Répartition Grive draine 2001 - 2005 Coordonnées GPS Lambert 93. 531 records from Colección de Referencia de Macroinvertebrados Bentónicos del Museo de Ciencias de la Universidad El Bosque. 990 records from Colección base (BGVPA) del Banco de germoplasma del Jardín Botánico Atlántico de Gijón. 93665 records from Butterflies of Ireland. 68396 records from CSIRO, Cruises, Vertebrate and Invertebrate Fishery Bycatch, North Australia, 1997. 46 records from New species of Helicopsyche von Siebold 1856 (Trichoptera: Helicopsychidae) from Brazil, including the redescription of Helicopsyche (Feropsyche) planorboides Machado 1957. 476 records from Anfibios y reptiles de la Sierra Montenegro-Las Trincheras y el cerro el Chumil, Morelos. 71 records from A checklist of the Cleridae of Iran with new data (Coleoptera: Cleroidea). 1118 records from ABC event data for Nyika Plateau, Buma Hills. 1 records from A new species of Pseudocrenilabrus (Perciformes: Cichlidae) from Lake Mweru in the Upper Congo River System. 72628 records from CAS Invertebrate Zoology (IZ). 41 records from Etude d'impact projet d’ouverture de carrière à Vaudoy-en-Brie. 5515 records from water Raw sequence reads. 15 records from See lilies of the genus Bathycrinus (Echinodermata, Crinoidea: Bathycrinidae) from the North-West Pacific hadal trenches. 6 records from Leafhopper tribe Coelidiini (Hemiptera: Cicadellidae: Coelidiinae) of the Indian subcontinent. 2 records from Rivulus uatuman sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new miniature killifish from the central Brazilian Amazon.. 102 records from Annotated catalog of the type specimens deposited at the fish collection of the “ Universidade Estadual Paulista, Câmpus de São José do Rio Preto ”, São Paulo, Brazil (DZSJRP). 805 records from Taxonomía y distribución de los filópodos (Crustacea: Branchiopoda, Anostraca, Notostraca, Spinicaudata y Laevicaudata) de México. 119 records from Suivi des leucorrines sur le site du Marais du Plata. 498 records from Kenai National Wildlife Refuge, Alaska (KNWR) Bird observations (Arctos). 5 records from NSW South Coast & ACT plants. 8848 records from EDP Baixo Sabor: Birds - Construction and Reservoir Filling Phases - Vilariça Stream (MC1) [2013-2014]. 433 records from Synthèse de la Répartition des populations de chamois en 1988 (réseau Ongulés sauvages ONCFS-FNC-FDC). 381 records from Relative abundance of T. quinqueloba in sediment core PS1243-1. 35 records from Ortsrand Zandershagen. 42 records from An der Weida zwischen Talsperre Zeulenroda und Vorsperre Weida. 1 records from Crickets of the genus Gryllus in the United States (Orthoptera: Gryllidae: Gryllinae). 1 records from Occurrence of mammalia relicts at site Ballybetagh. 2420 records from (Figure 10) Stratigraphic ranges of selected planktonic foraminifers at ODP Hole 101-631A. 4 records from The Odonata of Sulawesi and adjacent islands. Part 8. Revision of the genus Rhinocypha Rambur, 1842 (Chlorocyphidae). 505 records from National Frog Survey of Ireland 2010/2011. 1900 records from Colección Ornitológica de la Universidad del Valle. 10 records from Discoveries of the genera Baeochila and Idiocysta from Japan, with descriptions of two new species (Hemiptera: Heteroptera: Tingidae). 1 records from Museo Historia Natural UNAH VS (MUVS) Fish Collection. 260 records from Inventaire naturaliste de la commune de Papaichton (Guyane) : mission 2018. 6 records from Untangling convoluted taxonomy of Chambriella Rego, Chubb & Pavanelli, 1999 (Cestoda: Proteocephalidae), with erection of Riggenbachiella n. g. and the description of a new species from pimelodid catfishes in the Neotropical Region. 188 records from Données de Mammifères marins. Mission Sanctuaire AGOA de 2012 à 2014. 852 records from Waarneming.nl (NL) - Great Grey Shrike Count 2009-2010. 2962 records from Alterra (NL) - Microarthropods inventory in calcareous grasslands. 14 records from The Goblin spider genus Xestaspis in Sri Lanka (Araneae: Oonopidae). 1 records from Contributions to the taxonomy of Minixi Giordani Soika and Alphamenes Van der Vecht (Hymenoptera, Vespidae, Eumeninae), with an identification key to the species of the latter. 1 records from Deep-sea ascidians from Papua New Guinea. 19 records from Revision of the Neotropical genus Macreupelmus Ashmead (Hymenoptera: Chalcidoidea: Eupelmidae). 41676 records from Tagged Seal Location Data from SOGLOBEC. 1 records from (Table 1) Concentration of PCB and other contaminants in blood plasma of polar bears (Ursus maritimus) from Svalbard. 333 records from Données naturalistes de Renaud PUISSAUVE. 310556 records from Dry Tortugas Reef Visual Census 2010. 527 records from Suivi ornithologique par IPA et IKA réalisés dans la Réserve nationale de l’Étang de Saint-Paul en 2012 et 2014. 2623 records from Universidad de Murcia, Dpto. Biología Vegetal (Botánica), Murcia: MUB-HEPATICAE. 1 records from Discovery of the Dinoponera lucida male (Hymenoptera, Formicidae), a threatened giant ant from the Atlantic rain forest. 1709 records from The Gibson spider collection. 41 records from Ours 2008 présence Régulière Mailles_10km_LAEA Réseau Ours brun ONCFS. 56 records from Revision of the bee genus Bathanthidium Mavromoustakis (Hymenoptera: Apoidea Megachilidae: Anthidiini) with description of a new species from China. 8 records from A new pelvic-less species of Melanorivulus Costa (Cyprinodontiformes: Cynolebiidae), with a discussion on the pelvic-fin absence in killifishes. 8 records from Description of a new Penaeidae (Decapoda: Dendrobranchiata) species, Farfantepenaeus isabelae sp. nov.. 193 records from Truppenübungsplatz Panzerkaserne Böblingen. 1 records from The Calliphoridae (Diptera) of Armenia. 651 records from Réseaux écologiques/Trame verte et bleue. 14 records from Pseudoplesiops wassi, a new species of dottyback fish (Teleostei: Pseudochromidae: Pseudoplesiopinae) from the West Pacific.. 4 records from A new species of Neoperla (Plecoptera: Perlidae) from southeastern Tibet of China with additions to the knowledge of N. perspicillata Zwick, 1980. 66164 records from Florida Keys Reef Visual Census 1996. 8007 records from Segunda caracterización biológica de aves del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 3 records from Review of the genus Pseudolathra Casey, 1905 (Coleoptera: Staphylinidae: Paederinae) of Réunion Island. 22 records from Observations de tortues marines dans l'archipel de Saint-Pierre et Miquelon. 54 records from Données du/de la naturaliste Villalta Rémi provenant de la base de donnée du SINP Île-de-France CETTIA. 7 records from New species of the plesiomorphic genus Nixonia Masner (Hymenoptera, Platygastroidea, Platygastridae) from South Africa. 1 records from A new species of Eigenmannia Jordan & Evermann (Teleostei: Gymnotiformes: Sternopygidae) from Río Ventuari, Venezuela. 558 records from If_Ecologie_Conseil_2017_12_18. 264 records from Rescate de epífitas Oleoducto Bicentenario, Tramo Araguaney - Banadía (rescate). 1436 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase. 97 records from Monitoreo biológico en la cuenca La Paila, campaña ARA - RARE - CVC – Asociación Calidris. 1355 records from Antarctic Lakes Brine Raw sequence reads. 1 records from Lanlabeo duanensis, a new genus and species of labeonin fish (Teleostei: Cyprinidae) from southern China. 29 records from Occurrence of mammalia relicts at site Großes Schulerloch. 8 records from A review of the Neotropical microcaddisfly genus Acostatrichia Mosely, 1939 with description of a new species from Brazil (Trichoptera: Hydroptilidae: Leucotrichiinae). 93 records from Journal of Hymenoptera Research. 5938 records from Plan Aménagement et de Gestion Simplifié (PAGS) des forêts galeries des départements de l'Ouémé-Plateau. Data mobilized in the framework of a JRS Biodiversity Foundation project in Benin. 25 records from Inventario de Murciélagos Buenos Aires, Tauramena, Casanare. 143 records from Agromyzidae (Diptera: Schizophora) in the state of Pará: new species and new records in Brazil. 2985 records from Colección Entomológica CDMB. 3 records from NZCS Invertebrates New Collection After 1987. 182 records from (Fig. 10) Distribution of dinoflagellate cysts in Early Cretaceous sediments of DSDP Hole 41-367 in the North Atlantic. 16929 records from Lepidoptera (Specimens NRM). 216 records from Colección nacional de palmas de Colombia - JBQ. 822 records from Las comunidades de myxomicetes de selva baja caducifolia. 182049 records from Florida Keys Reef Visual Census 1999. 781 records from Composición florística y estructura de tres parcelas permanentes en diferentes estados sucesionales en transición de bosques húmedos tropicales con bosques secos tropicales del municipio de Lebrija, Santander (Primer censo). 2 records from Two new species of Helicopsyche Siebold 1856 (Insecta: Trichoptera: Helicopsychidae) from Pará State, northern Brazil. 9 records from Steinbock (1937) Turbellaria XIV. The fishery grounds near Alexandria. Notes and Memories of the Fisheries Directorate of Egypt, No. 25. 10 records from Occurrence of mammalia relicts at site Meiendorf. 187 records from Tachinid Recording Scheme - GB and Ireland records. 5 records from Thoridae (Crustacea: Decapoda) can penetrate the Abyss: a new species of Lebbeus from the Sea of Okhotsk, representing the deepest record of the family. 3 records from Denitrification bacteria in sediment cores of Daya Bay, China. 1 records from Siccia imana, a new species from Rwanda (Lepidoptera: Erebidae: Arctiinae). 9 records from A new species of Proterhinus Sharp, 1878 (Coleoptera: Curculionoidea: Belidae) from Miti‘aro, Cook Islands, South Pacific. 869 records from Programme ACT : Répartition Grive musicienne 2005 - 2009 Coordonnées GPS Lambert 93. 13969 records from University of Colorado, Museum of Natural History Herbarium Bryophyte Collection. 1962 records from DREAL_PACA_-_N2000_-_Parc_Naturel_Régional_du_Verdon_2017_12_18. 131 records from Occurrence of mammalia relicts at site Bocksteinschmiede. 31 records from Mesostigmatic mites (Acari: Mesostigmata) of Saudi Arabia (excluding Phytoseioidea), new records and a key to the known species. 1 records from Description of the larva of Orthemis ferruginea (Fabricius, 1775) (Odonata: Libellulidae). 96 records from (Table 1.2.1.1) Abundance of sympagic meiofauna of sea-ice core PS69/574-1. 2510 records from Kenya Wildlife Service, Laikipia Samburu Aerial Census, 2012. 18 records from An interactive key to Central European species of the Pteromalus albipennis species group and other species of the genus (Hymenoptera: Chalcidoidea: Pteromalidae), with the description of a new species. 193444 records from Arizona State University Vascular Plant Herbarium. 85 records from Frohlinder Mühlenbach (Dortmund-Kirchlinde). 3 records from Two new species of tribe Agalliini (Hemiptera: Cicadellidae: Megophthalminae) with note on intraspecific variations. 1894 records from Fungi Collection. 2 records from Oribatids from Switzerland II. (Acari: Oribatida). (Acarologica Genavensia XC). 87 records from Données espèces - Expertise IPE 70. 3 records from A new species of the flower bug genus Orius Wolff (Hemiptera: Anthocoridae) cryptically inhabiting Hibiscus tiliaceus L. (Malvaceae). 20 records from A review of the genus Beltia Jacoby (Chrysomelidae: Eumolpinae: Eumolpini), with descriptions of fourteen new species from Costa Rica, Panama, and northwestern South America. 191 records from Steinbruch Mainz-Weisenau, 2. Jahr. 8635 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Lichens. 2172 records from ConDidact Citizen Science Surveys - Snails 2006. 109 records from Birdrace-Di_Bi_Di_Birder-Wesel. 6 records from Five new species of Nazeris Fauvel in Guangxi, China (Coleoptera, Staphylinidae, Paederinae). 5 records from Données naturalistes de Mikaël PAILLET. 4607 records from Données de type contact en Guadeloupe. 1 records from The Pselaphodes (Coleoptera: Staphylinidae: Pselaphinae) of Nepal. 687 records from The Sphecid Wasps of the genus Cerceris L, 1802 of the " Biologiezentrum Linz " - Collection in Linz, Austria, from the Palearctic Region (part II). (Hymenoptera, Apoidea, Crabronidae). 7 records from New and little known species of Eumolpinae (Coleoptera: Chrysomelidae) from Northern Vietnam. 15 records from Three new species of Holoscolex (Clitellata, Glossoscolecidae) from the Gurupi Biological Reserve, last forest remnant of the Belém Endemism Area, Eastern Amazon. 6 records from New species of Anaptomecus Simon, 1903 (Araneae: Sparassidae) from Colombia, with an identification key for all known species of the genus. 1596 records from Microbial communities in deep eastern Mediterranean Sea surface sediments. 2053 records from Atlas des Poissons et Crustacés d'eau douce de Guadeloupe. 31 records from Ecosystems of the sandstone region incl. sand-belt (SE of Melb.). 1037 records from Evaluación del estado actual de las poblaciones silvestres de chigüiros (Hydrochoerus hydrochaeris) en los municipios de Paz de Ariporo y Hato Corozal, Casanare. 8 records from A new species of Cetopsis from the Guiana Shield (Siluriformes: Cetopsidae: Cetopsinae). 640 records from Annales de la Société Linnéenne de Maine-et-Loire. 130 records from New species of Ilanga (Gastropoda: Trochoidea: Solariellidae) from the Indo-West Pacific. 116 records from Données de Mammifères marins dans les TAAF et autres territoires issues de la bibliographies. Compte cardobs 1007 (Trudelle). 7 records from Diversification in the mountains: a generic reappraisal of the Western Ghats endemic gecko genus Dravidogecko Smith, 1933 (Squamata: Gekkonidae) with descriptions of six new species. 53 records from Données malacologiques continentales de Julien Ryelandt (CORSE 2017). 12451 records from Insectes Hétéroptères Mirides de France. 1 records from Macrochelid mites (Mesostigmata: Macrochelidae) from São Paulo state, Brazil, with description of a new species of Macrocheles. 23 records from The genus Leucophenga (Diptera, Drosophilidae), part VII: the subpollinosa species group from China, with morphological and molecular evidence. 1552 records from Données du naturaliste ROCHAT Didier provenant de la base de donnée du SINP Île-de-France CETTIA. 3 records from Taxonomic notes on the tribe Dryptini Bonelli, 1810 with description of a new genus and specie
Keywords: GBIF; biodiversity; species occurrences